The high‑resolution bathymetric dataset of the Saudi Arabian Red Sea margin from the 2022 Red Sea Decade Expedition - Marchese, Fabio; Nolan, Megan; Dunn, Natalie; Watts, Marta; von Krusenstiern, Katherine; Foy, Craig; Rodrigue, Mattie; Pieribone, Vincent; Qurban, Mohammed; Duarte, Carlos; Benzoni, Francesca (European Organization for Nuclear Research, 2026)
Gridded multibeam bathymetry of the Saudi Arabian Red Sea collected during the 2022 Red Sea Decade Expedition (funded by the National Center for Wildlife, Kingdom of Saudi Arabia). The QPS Qimera software license was provided by King Abdullah University of Science and Technology (KAUST) through baseline funding awarded to Francesca Benzoni (BAS/1/1090-01-01). The dataset includes one 40 m resolution model covering the full deep-water survey area, acquired by the Kongsberg EM 304 aboard the M/V OceanXplorer (OCX), and four 5 m resolution models of shallow-water bathymetry acquired by the Teledyne RESON SeaBat T50-P aboard Metalshark38 (MS), one per expedition Leg (L1 to L4).
Keywords: Bathymetry; High resolution; Indian ocean; License; Margin (machine learning); dept.egm

Assessing the risk of contaminated sediments during small dam removal projects in the Long Island Sound watershed - Alix, Katelyn; Fedorchuk, Nicholas; Breslin, Vincent; Hoehne, Gary; Hayton, Jam; Balbachan, Kayla (Geological Society of America, 2025)
Keywords: Computer science; Contamination; Ecology; Environmental science; Geology; Geotechnical engineering; Hydrology (agriculture); Oceanography; Sound (geography); Watershed; dept.egm; dept.esc

Ingested Plastic in the Great Northern Diver, the Common Loon (Gavia immer) - Hilling, Thomas P.; Reynolds, Hannah T.; Breslin, Vincent T.; Pokras, Mark A. (Northeastern Naturalist, 2025)
Plastic pollution and its impact on water-reliant avifauna is a global, pervasive issue. We evaluated necropsy data of Gavia immer (Common Loon) from freshwater and marine environments in the northeastern US from 2011 to 2022, and found 16.2% (106/654) had ingested plastic items (macroplastics). We examined Common Loons stranded from 2020 to 2022, quantified macroscopic plastic items in detail, and processed the ingesta for suspected microplastics. We found macroplastics in 20.7% (11/53) and suspected microplastic particles, predominately clear fibers, in 100% (37/37) of the Common Loons. While we found no evidence that sex, mass, or geography correlated with microplastic load, both macroplastics and suspected microplastics were widespread and prevalent in Common Loon ingesta in the northeastern US. © 2025 Humboldt Field Research Institute. All rights reserved.
Keywords: dept.egm

Local scale climate change variability in New England, United States - Miller, Matthew (Climatic Change, 2025)
Keywords: Cartography; Climate change; Climatology; Ecology; Environmental science; Geography; Geology; Interpolation; Mathematics; Meteorology; New England; Oceanography; Physical geography; Precipitation; Scale (ratio); Spatial ecology; Spatial variability; Statistics; Temperature; Variation (astronomy); dept.egm; peer-reviewed

Divided by a common language? The impact of a joint international field trip on student skills - Lane, Timothy; Rourke, Maeve; Kelly, Miriah; Graves, Scott; Dalrymple, Sarah; Dick, Jonathan; Matthews, Tom; Onnis, Patrizia; Slomba, Jeff; Pétursson, Ólafur; Heidkamp, C. (Journal of Geography in Higher Education, 2025)
Fieldwork is often cited as one of the most important and effective parts of geography education, despite increasing scrutiny over its environmental and financial cost. As a result, it is imperative that any overseas fieldwork is as impactful as possible, enabling deep experiential learning. Here, we investigate the success of a joint field trip (Liverpool John Moores University, UK and Southern Connecticut State University, USA) to East Iceland. Such field trips are rare but have the potential to be extremely impactful on both cohorts of students. We outline the origins of the field trip, the considerations taken into account during planning, and the student skills we embedded into teaching. Surveys and interviews demonstrated that the field trip was highly successful, with students reporting excellent development of environmental and global awareness as well as research and leadership skills. Students also developed strong, lasting social networks, including those in the alternate university, and in Iceland. Cohorts responded similarly, suggesting that the trip presents similar opportunities to all students. We demonstrate that undertaking a joint field trip can deliver huge benefits to students, becoming a “perspective changing, and a once in a lifetime opportunity” affecting future study and career choices.
Keywords: Civil engineering; Engineering; Field (mathematics); Geography; Joint (building); Mathematics education; Pedagogy; Psychology; dept.egm; fieldwork; higher education; pedagogy; peer-reviewed; skills development

Neptune’s domain: a political geography of the sea - Glassner, M.I. (Neptune’s Domain: A Political Geography of the Sea, 2024)
First published in 1990, Neptune’s Domain is organized around one unifying theme: the geographic aspects of the new Law of the Sea as expressed primarily in the United Nations Convention on the Law of the Sea. The first two chapters provide essential background information. Chapters 3 through 9 explain relevant provisions of the Convention. The next two chapters cover topics excluded from the Convention, and the last three chapters are more analytical and future-oriented. All students and scholars concerned with the human use of the marine environment will welcome this book, whether they be geographers, political scientists or lawyers. © Martin Ira Glassner 1990. All rights reserved.
Keywords: dept.egm

Sustainability after COVID-19: pillars for a just transition - Morrissey, John; Heidkamp, Patrick (Environmental Sustainability, 2022)
The vulnerability of the global economy has been starkly exposed by the COVID-19 pandemic. Longer term thinking and new approaches to development and prosperity are urgently required. In this paper, we forward a series of principles on which economic and development policy for the post-COVID era should be developed. These are outlined as five ‘pillars’ from which to rebuild the global economy, based on principles of a shared sustainable prosperity. These pillars are: (I) an ecological prosperity; (II) a decarbonized economy; (III) a shared cost burden; (IV) a governance new deal; (V) a just resilience. In outlining the ‘5 pillars’ we explicitly recognize that sustainability cannot simply be a ‘green’, or environmental concern. Social and economic dimensions of sustainability are key for societal stability and continuity. This is made ever starker in the context of the fundamental economic and societal restructuring forced by the disruption of the COVID-19 pandemic. In this regard, the pillars represent a triple bottom line framing of sustainability, of mutually supportive domains of economic, social and environmental well-being. The five pillars are informed by principles of distributive and procedural justice, recognizing the importance and advantages of real community engagement and empowerment and giving due respect and deference to the ecological carrying capacity of our fragile planet. We argue that the post-COVID-19 re-build represents a once-in-a generation opportunity to markedly shift developed trajectories to more sustainable pathways, to rebalance the domains of sustainability, and in the process, to address longer-term crises including those of climate and biodiversity loss.
Keywords: COVID-19; Climate crisis; Prosperity; Resilience; Social justice; Sustainability; dept.egm; peer-reviewed

Blue Economy - Germond-duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2023)
Keywords: dept.egm

Introduction - Morrissey, John; Heidkamp, C. Patrick; Garland, Michaela; Krak, Louie (Demanding Sustainability: Pillars to (Re-)Build a Shared Prosperity, 2022)
This chapter introduces the 5 ‘pillars’ through which to (re-)build a shared sustainable prosperity. The five pillars aim to provide a framework through which policymakers, decision-makers, politicians, community groups and the corporate sphere might begin to consider, map out and plan for just transitions in their domains. The theoretical framing combines socio-technical transitions, social justice and just transitions perspectives; the novelty of our proposed approach here is the further inclusion of resilience perspectives, to account for the shifting relations between sustainability and resilience. Our understanding of sustainability aligns with a ‘strong sustainability’ perspective, whereby ecological limits represent ‘hard’ limits to development, limits which need to be acknowledged and respected.
Keywords: Just transitions; Pillars; Social justice; Socio-technical transitions; Strong sustainability; Sustainable prosperity; dept.egm

Shifting Sustainable Lifestyle Practices and Behaviour During Times of Pandemic Disruptive Change: Implications for on-Going Socio-Technical Transitions - Axon, Stephen; Lent, Talia; Njoku, Anuli (Energy Research & Social Science, 2023)
COVID-19 has extensively reshaped lifestyle practices, supply chain dynamics, and climate mitigation efforts. The resulting crises from the pandemic in relation to local and community sustainability practices have not yet been investigated in depth. There is a need to explore the individual characteristics and responses from rapid transitions of lifestyles at various scales. Analysing how the COVID-19 pandemic has shaped and altered sustainable living practices, and the motivations supporting them, has yet to be determined but is crucial to gain further insight to improve management responses to large-scale disruptive change. Presenting empirical findings from semi-structured interviews in New Haven County, Connecticut, this study elucidates the ways in which the lifestyles have been altered and how they responded while specifically highlighting the consequences for behavioural routines and sustainable lifestyle practices. As a result of lockdowns and pandemic mitigation responses, individual sustainability engagement fluctuated with participants shifting dietary, mobility, and energy and food consumption patterns. Specifically, participants emphasised substantial decrease in daily travel during initial phases of the pandemic alongside increased online shopping and energy use at home. Though changes to consumption practices were replaced former habits with unsustainable ones, individuals also noted how they co-opted the pandemic over time to pursue sustainable actions at home. As a macro-level ‘window of opportunity’ and disruptive change, this study illustrates how sustainable lifestyle practices were reshaped; some by choice, some by force, and some reflecting a forced choice. These findings have clear implications for the stability of maintaining sustainable practices influenced by landscape-level shocks.
Keywords: Behaviour change; COVID-19; Energy use; Food consumption; Social practices; Transport; dept.egm; dept.pch; peer-reviewed

History of Geography as a Science in the Republic of Paraguay. - Yacher, Leon I. (2010)
Keywords: dept.egm; faculty_collection; sabbatical_report

Henry's F. Pittier's Contributions to the Geography of Costa Rica and Venezuela. - Yacher, Leon I. (1995)
Keywords: dept.egm; faculty_collection; sabbatical_report

A Wholistic View of Environmental Education. Rationale. - Stone, A. Harris (Spring ; Center of the environment., 1991)
Keywords: dept.egm; faculty_collection; sabbatical_report

Law of the Sea. - Glassner, Martin Ira (1989)
Keywords: dept.egm; faculty_collection; sabbatical_report

Basic Botany - Avery, David F.; Smith, Dwight G. (Simon and Schuster Custom Publishing, 1994)
Keywords: Botany; dept.egm; faculty_collection

Towards Coastal Resilience and Sustainability - Heidkamp, C. Patrick; Morrissey, John; Graves, Scott M. (Dynamics of economic space, 2019)
"Coastal zones represent a frontline in the battle for sustainability, as coastal communities face unprecedented economic challenges. Coastal ecosystems are subject to overuse, loss of resilience and increased vulnerability. This book aims to interrogate the multi-scalar complexities in creating a more sustainable coastal zone. Sustainability transitions are geographical processes, which happen in situated, particular places. However, much contemporary discussion of transition is either aspatial or based on implicit assumptions about spatial homogeneity. This book addresses these limitations through an examination of socio-technological transitions with an explicitly spatial focus in the context of the coastal zone. The book begins by focusing on theoretical understandings of transition processes specific to the coastal zone and includes detailed empirical case studies. The second half of the book appraises governance initiatives in coastal zones and their efficacy. The authors conclude with an implicit theme of social and environmental justice in coastal sustainability transitions. Research will be of interest to practitioners, academics and decision-makers active in the sphere of coastal sustainability. The multi-disciplinary nature encourages accessibility for individuals working in the fields of Economic Geography, Regional Development, Public Policy and Planning, Environmental Studies, Social Geography and Sociology" -- Provided by publisher's website.
Keywords: Coastal zone management; Economic aspects; Economic aspects; Sustainable development; dept.egm; faculty_collection

Sabbatical leave report: Spring 2014 - Heidkamp, C. Patrick (2014)
The proposed research project focused on analyzing food system resilience in a small town in eastern Iceland from the perspective of environmental economic geography. In addition to the stated project Heidkamp initiated "a new research project focused on the uniqueness of Nordic Environments, Nordic Spaces and Nordic Places." The sabbatical study yielded panelist and lecturer invitations and conference papers and presentations.
Keywords: dept.egm; faculty_collection; sabbatical_report

Raptors of the Northeast - Bosakowski, Thomas; Smith, Dwight G. (Coachwhip Publications, 2010)
Keywords: Birds of prey; Identification; Identification; Birds; Northeastern States; dept.egm; faculty_collection

Sabbatical leave report: sabbatical Spring 2010 - Yacher, Leon I. (2010)
The purpose of the project was to travel to Paraguay to explore the history of geography as a science in that country, including identifying the foremost geographers who helped introduce and establish geography as a science in that country. No such study on the history of geography in Paraguay had been previously undertaken anywhere. Further research will be needed, but the collected material is ample for at least two article-length publications.
Keywords: dept.egm; faculty_collection

Russia in Transition: Coverage by American Newspapers in the 1990s: Geography, Ideology, and Emotion in the Narration of Political-Economic Change - West, Eric (Vdm Verlag, 2009)
Keywords: 1991-; Mass media; Political aspects; Politics and government; Russia (Federation); Foreign news; Russia (Federation); Russia (Federation); dept.egm; faculty_collection

And Life Is Changed Forever: Holocaust Childhoods Remembered - Glassner, Martin Ira; Krell, Robert; Holocaust Child Survivors of Connecticut (Landscapes of childhood, 2006)
Contains brief memoirs, some of which describe experiences in the Holocaust. Includes commentary by psychologist and child survivor Robert Krell. Partial contents:
Keywords: Biography; Holocaust, Jewish (1939-1945); Connecticut; History and criticism; Influence; Holocaust, Jewish (1939-1945); Jewish children in the Holocaust; Personal narratives; Personal narratives; Holocaust survivors; dept.egm; faculty_collection

All Possible Worlds: A History of Geographical Ideas - Martin, Geoffrey J. (Oxford University Press, 2005)
Keywords: Geography; History; dept.egm

The Role of Geographer and Natural Scientist Henri Francois Pittier (1857-1950) in the Evolution of Geography as a Science in Costa Rica - Yacher, Leon I. (Mellen studies in geography ; v. 12, 2004)
Keywords: Costa Rica; History; History; Geography; Influence; Geography; Latin America; Pittier, Henri, 1857-1950; award_winner; dept.egm

Plants - Avery, David F.; Smith, Dwight G.; Schultz, Marcia H. (Pearson Custom Publishing, 2003)
Keywords: Botany; Plants; dept.egm; faculty_collection

Raptors of the Pacific Northwest - Bosakowski, Thomas; Smith, Dwight G. (Frank Amato Publications, 2002)
Keywords: Birds of prey; Identification; Northwest, Pacific; Northwest, Pacific; Birds of prey; dept.egm; faculty_collection

Great Horned Owl - Smith, Dwight G. (Wild bird guides, 2002)
Keywords: Great horned owl; dept.egm; faculty_collection

Bibliography on Land-Locked States, Economic Development and International Law - Glassner, Martin Ira (M.E. Sharpe, 2001)
Keywords: Bibliography; Bibliography; Access to the sea (International law); Landlocked states; dept.egm; faculty_collection

Plant Life - Smith, Dwight G.; Avery, David F.; Schultz, Marcia H. (Southern Connecticut State University ; Pearson Custom Pub., 2000)
Keywords: Nomenclature; Plants; Plants; dept.egm; faculty_collection

Connecticut Birding Guide - Devine, Arnold; Smith, Dwight G. (Thompson-Shore, 1996)
Keywords: Birding sites; Connecticut; Guidebooks; Guidebooks; Bird watching; dept.egm; faculty_collection

Political Geography - Glassner, Martin Ira (J. Wiley, 1996)
Keywords: Political geography; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff, 1995)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; dept.egm; faculty_collection

Zoology Laboratory Guide - Avery, David F.; Nelson, Vernon A.; Pellegrino, Peter Edward; Smith, Dwight G.; Turko, Alexander A.; Burian, Steven K.; Green, Laura A.; Duman, Mathew (Southern Connecticut State University, 1994)
Keywords: Laboratory manuals; Zoology; dept.egm; faculty_collection

All Possible Worlds: A History of Geographical Ideas - Martin, Geoffrey J.; James, Preston E.; James, Eileen W. (Wiley & Sons, 1993)
Keywords: Geography; History; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Sold and distributed in the U.S.A. and Canada by Kluwer Academic Publishers, 1991)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

Neptune's Domain: A Political Geography of the Sea. - Glassner, Martin Ira (1990)
Keywords: Maritime law; Political geography; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Academic Publishers, 1986)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

International Law of the Sea and Marine Affairs: A Bibliography. Supplement to the 1980 Edition - Papadakis, N.; Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Boston, 1984)
Keywords: Bibliography; Maritime law; dept.egm; faculty_collection

Global Resources: Challenges of Interdependence - Glassner, Martin Ira (Published for the Foreign Policy Association by Praeger, 1983)
Keywords: Natural resources; award_winner; dept.egm; faculty_collection

Baseline Shellfish Data for the Assessment of Potential Environmental Impacts Associated with Energy Activities in Connecticut's Coastal Zone - Pellegrino, Peter Edward; Hubbard, William A. (Southern Connecticut State University Foundation, 1983)
Keywords: Connecticut Coastal Energy Impact Program; Shellfish populations; Effect of oil spills on; Environmental aspects; Long Island Sound (N.Y. and Conn.); Long Island Sound (N.Y. and Conn.); Aquatic ecology; Long Island Sound (N.Y. and Conn.); Energy industries; Long Island Sound (N.Y. and Conn.); Petroleum products; Long Island Sound (N.Y. and Conn.); Shellfish; Research; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (Sijthoff & Noordhoff, 1980)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Maritime law; dept.egm; faculty_collection

Systematic Political Geography - Glassner, Martin Ira; De Blij, Harm J. (Wiley, 1980)
Keywords: Political geography; Geopolitics; dept.egm; faculty_collection

The Life and Thought of Isaiah Bowman. - Martin, Geoffrey J. (1980)
Keywords: Biography; Bowman, Isaiah, 1878-1950; Geographers; United States; award_winner; dept.egm; faculty_collection

Faculty Bibliography - Clarie, Thomas C.; Koch, Róbert; Yacher, Leon I.; Sandomirsky, LNatalie (Southern Connecticut State University, 1978)
Keywords: Bibliography; Faculty; Southern Connecticut State University; dept.art; dept.egm; dept.lib; faculty_collection

Working Bibliography of Owls of the World: With Summaries of Current Taxonomy and Distributional Status - Clark, Richard J.; Smith, Dwight G.; Kelso, Leon H. (National Wildlife Federation scientific & technical series ; no. 1, 1978)
Keywords: Bibliography; Owls; dept.egm; faculty_collection

The Association of American Geographers, the First Seventy-Five Years, 1904-1979 - James, Preston E.; Martin, Geoffrey J. (The Association, 1978)
Keywords: Association of American Geographers; dept.egm; faculty_collection

Marriage Migration and Racial Mixing in Colonial Tlazazalca, (michoacán, Mexico), 1750-1800 - Yacher, Leon I. (Discussion paper series (Syracuse University. Department of Geography) ; no. 32, 1977)
Keywords: Case studies; Case studies; Endogamy and exogamy; Marriage; Mexico; Tlazazalca (Michoacán); dept.egm; faculty_collection

Man and the Earth. - Hoyt, Joseph Bixby (Prentice-Hall, 1973)
Keywords: Human ecology; Geography; dept.egm; faculty_collection

Ellsworth Huntington; His Life and Thought, - Martin, Geoffrey J. (Archon Books, 1973)
Keywords: Huntington, Ellsworth, 1876-1947; SCSU Faculty Scholar Award; award_winner; dept.egm; faculty_collection

Access to the Sea for Developing Land-Locked States. - Glassner, Martin Ira (Nijhoff, 1970)
Keywords: Access to the sea (International law); Landlocked states; Developing countries; Commerce; award_winner; dept.egm; faculty_collection

Mark Jefferson, Geographer, - Martin, Geoffrey J. (Eastern Michigan University Press, 1968)
Keywords: Jefferson, Mark, 1863-1949; dept.egm; faculty_collection

The Mark Jefferson Paris Peace Conference Diary - Jefferson, Mark; Martin, Geoffrey J. (University Microfilms, 1966)
Keywords: Paris Peace Conference (1919-1920)--Personal narratives; World War, 1914-1918; Peace; dept.egm; faculty_collection

Man and the Earth. - Hoyt, Joseph Bixby (Prentice-Hall geography series, 1962)
Keywords: Human geography; dept.egm; faculty_collection

Africa in Maps. - Martin, Geoffrey J. (W. C. Brown Co, 1962)
Keywords: Africa; Maps; dept.egm; faculty_collection

Geography of Connecticut - Hoyt, Joseph B. (1958)
Keywords: Connecticut; Geography; dept.egm; faculty_collection

Blue Economy - Germond-Duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2016)
Geography has engaged in insightful discussions on how to understand, analyze, criticize, and implement the blue economy. United Nations agencies, Small Island Developing States, and increased academic interest in oceans have played important roles in the global adoption of the blue economy idea, that is, the sustainable exploitation of marine and coastal resources. Geographical research on the blue economy has addressed key themes such as economic and political discourse, relational thinking and assemblage, sustainability and just transitions, and blue economy risks.
Keywords: coastal and marine geography; dept.egm; economic development; environmental management; sustainable development

Demanding Sustainability: Pillars to (Re-)Build a Shared Prosperity - Morrissey, John; Heidkamp, C. Patrick (Springer International Publishing, 2022)
Keywords: Climate Crisis; Covid; Covid-19; decarbonized economy; dept.egm; ecological prosperity; global economy; just resilience; resilience; social justice; sustainable governance; sustainable prosperity

Ch. 1 - Blue Economy: People and Regions in Transitions - Heidkamp, C.P.; Morrissey, J.; Germond-Duret, C.; Rourke, M. (Blue Economy: People and Regions in Transitions, 2022)
Keywords: dept.egm

(In)justice and the blue economy - Germond-Duret, Celine; Heidkamp, C. Patrick; Morrissey, John (The Geographical Journal, 2022)
While the ocean space has long been ignored by social sciences, the past 15 years have witnessed an increased interest in the marine environment by scholars in Human Geography. The academic literature on the blue economy, almost non-existent a few years ago, is now burgeoning. The academic debate has offered some critical assessment of blue economy initiatives, but more needs to be done to address the true place of environmental protection within a blue economy, and to put people at the centre of concerns and analyses. Of particular concern, is the ambiguity of the blue economy concept and the confusion over its social and environmental sustainability, which can ultimately result in harmful practices. An important question is then how should social scientists in general and geographers, specifically, engage with these debates, and in particular how should the potential human and social costs of the blue economy be investigated and addressed while assuring justice and fairness? The papers presented here share the vision that environmental sustainability, justice and equality should be at the heart of the blue economy; not just conceptually, but practically too. The papers pursue efforts to identify blue economy risks and the mechanisms through which they occur; assess the place of inclusion and participation in a sustainable blue economy; define what blue economy policies should include to drive just and sustainable practices; and identify where the dominant understandings of the blue economy and its priorities are coming from. In other words, they put considerations of justice and broader cultural structures at the centre of their concerns and analysis. They also highlight the need to bypass geographical boundaries and gain insights from other disciplines and methodologies to grasp such an encompassing concept, and foster not just a blue economy with social justice, but a blue economy for social justice.
Keywords: blue economy; communities; dept.egm; justice; peer-reviewed; sustainability

Breaking Blue: Establishing comprehensive policy for a just and inclusive transition for the Blue Economy - Axon, Stephen; Collier, Sammy (Marine Policy, 2023)
At a time of substantial interest in the Blue Economy, it is surprising that sustainability dilemmas and justice components are not well integrated within its academic discourse or policy arena. Reviewing a number of existing U.S. coastal and marine policies, we identify that justice and equity components are essentially missing and advocate for a comprehensive policy framework for a just and inclusive transition for the Blue Economy. Looking forward, we review and critique the policy proposal of Elizabeth Warren’s Blue New Deal. While the current state of the Blue New Deal remains uncertain, we indicate that such a policy framework would integrate justice, equity and inclusivity as part of operationalising the Blue Economy. Given the proposal for a Blue New Deal is relatively new, we propose a research agenda to explore how comprehensive policy frameworks may seek to place justice and inclusivity at the centre of the Blue Economy.
Keywords: Blue Economy; Blue Justice; Blue New Deal; Governance; Sustainability; dept.egm; peer-reviewed

Geographical considerations for capturing value in the U.S. sugar kelp (Saccharina latissima) industry - Heidkamp, C. Patrick; Krak, Louie Vincent; Kelly, Miriah M. Russo; Yarish, Charles (Marine Policy, 2022)
The United States’ seaweed industry is worth over $300 million annually thanks in part to the rising popularity of seaweed-based products. Seaweed has myriad uses and great potential for novel product innovation and development while also providing numerous environmental benefits including carbon and nitrogen sequestration and other crucial ecosystem services . One of the most promising and prevalent species under domestic cultivation is Saccharina latissma. Also known as sugar kelp, this abundantly grown cold-water species dominates the edible seaweed market in the United States . This paper provides an in-depth geographical analysis of the current state of the U.S. sugar kelp industry, comparing regional market differences and opportunities for growth in Maine, Alaska, and Connecticut. Data was collected from the 2020 National Sea Grant Seaweed Symposium (https://seaweedhub.org/symposium/) and through a series of semi-structured interviews with key industry participants, yielding insights into the challenges that seaweed stakeholders face across the country. Proposed solutions for increasing the profitability of sugar kelp are explored and include market differentiation through regional origin labels, eco-labels, and quality labels.
Keywords: Eco-labels; Ecosystem services; Market differentiation; Origin labels; Quality labels; Seaweed; Sugar kelp; dept.egm; peer-reviewed

Beyond stakeholder engagement in the coastal zone: Toward a systems integration approach to support just transformation of the blue economy - Kelly, Miriah M. Russo (The Geographical Journal, 2022)
Transformation has become a prevailing and desirable concept in blue economy literature. In parallel, researchers have been considering ways to effectively engage stakeholders to support just transformational agendas. Globally, coastal communities are already being affected by the inevitable impacts of climate change and changes to the blue economy. These pressures present complex contexts for coastal zone stakeholder engagement. In this paper, I argue that taking a systems integration approach to interacting with stakeholders is needed to support just transformational change. Assessing stakeholder systems and their relationship to coastal resources is imperative for understanding dynamics that may promote or hinder just transformation. Taking an adaptive management approach to working alongside stakeholders through transitional processes, thus building capacity, is needed to generate momentum toward just transformational change. Lastly, I explain how applications of the subsidiarity principle in integrating stakeholder systems can support a just transformational process and can inform more durable transformational outcomes.
Keywords: blue economy; coastal; dept.egm; just transition; peer-reviewed; stakeholder; systems integration; theoretical model

How Connecticut pediatricians view polluted air - Kane, D.N. (Connecticut Medicine, 1978)
Keywords: Air Pollution; Attitude of Health Personnel; Connecticut; Pediatrics; air pollution; dept.egm; editorial; ⛔ No DOI found

Systematic political geography. 4th edition - Glassner, M.I.; De Blij, H.J. (Systematic political geography. 4th edition, 1988)
The fourth edition of this text has been thoroughly updated and includes expanded chapters on Antarctica and outer space as well as new chapters on the geography of elections and the geography of war and peace. A chapter is devoted to outlaws and merchants of death which covers piracy, drug trafficing, the arms trade, and terrorism. Other additions include coverage of international economic sanctions, transnational corporations, refugees, and pollution across international boundaries. -from Publisher
Keywords: arms trade; dept.egm; economic sanctions; elections; peace; political geography; pollution; refugees; terrorism; war; ⛔ No DOI found

Classifying Aquatic Habitats - Smith, D.G.; Leskowitz, I. (American Biology Teacher, 1987)
Keywords: dept.egm

John Paul Goode, 1862-1932. - Martin, G.J. (Geographers: biobibliographical studies, vol. 8, 1984)
In 1901 Goode obtained his doctorate - only the second in the USA to break away from the geology/physiography tradition. As his career developed he increasingly specialized in cartography, developed coloured wall maps for Rand McNally, and an interrupted homolosine projection. His name has survived on a school atlas for over 60 years. There is a chronological bibliography and a summary of his life.-K.Clayton
Keywords: dept.egm; ⛔ No DOI found

Navigational restrictions within the new LOS contexts: Georgaphical Implications for the United States. Lewis M. Alexander, Peace Dale, RI: Offshore Consultants, Inc., December 1986 - Glassner, M.I. (Political Geography Quarterly, 1991)
Keywords: dept.egm

Foxwoods Casino Resort: An unusual experiment in economic development - D'Hauteserre, A.-M. (Economic Geography, 1998)
The Foxwoods Casino Resort owned by the Mashantucket Pequots of Connecticut is the largest gambling casino in the Western world. The Pequots' Connecticut location enabled the tribe to open a casino, with accessibility to a large market and limited competition. The opening of Foxwoods is also the result of changes in relationships between Americans and Indians and shifts in American attitudes toward gambling. As attitudes and laws change, however, there is little chance that another Indian Foxwoods will be created here or elsewhere in the United States.
Keywords: American Indian sovereignty; Connecticut; Gambling; Mashantucket Pequots; Pequots people; USA, Connecticut; casino; dept.egm; gambling; indigenous population; recreational activity

Three new species of Jaltomata (Solanaceae) from Ancash, Peru - Mione, T.; Leiva G., S.; Yacher, L. (Novon, 2000)
Three new Jaltomata species from the department of Ancash, Peru, are described and illustrated. The three species are distinguished from others in the genus by features of the flowers, hairs, and leaves. Fruits of Jaltomata cajacayensis S. Leiva and Mione are gathered for consumption. Jaltomata lomana Mione and S. Leiva is known only from a single fog-dependent plant community, a lomas formation. Jaltomata yungayensis Mione and S. Leiva is widely distributed at high elevations.
Keywords: Jaltomata; Jaltomata cajacayensis; Jaltomata lomana; Jaltomata yungayensis; Magnoliophyta; Solanaceae; dept.egm

The lead project. An environmental instrumental analysis case study - Breslin, V.T.; Sañudo-Wilhelmy, S.A. (Journal of Chemical Education, 2001)
Keywords: dept.egm; peer-reviewed

Jaltomata andersonii (Solanaceae): A new species of Peru - Mione, T.; Leiva G., S.; Yacher, L. (Rhodora, 2004)
Jaltomata andersonii (Solanaceae), here named, is distributed on the western slope of the Andes, in the Departments of Ancash and Lima, Peru, from 2300 to 3400 m of elevation. This species differs from others of the genus by having an unarticulated axis connecting the flower to the plant where all others have both a peduncle and a pedicel. The following combination of features also characterize this species: the hairs of leaves and axes are gland-tipped; the petiole is no longer than 1 cm; the flowers are solitary; the corolla is broadly crateriform-rotate, purple, and up to 3.7 cm in diameter; and the filaments are extremely villous at their bases.
Keywords: Andes; Corolla; Flora of Peru; Jaltomata; Jaltomata andersonii; Magnoliophyta; Solanaceae; dept.egm; ⛔ No DOI found

Photojournal: Venezuela - Yacher, L. (Focus on Geography, 2007)
Keywords: South America; Venezuela; dept.egm; imagery

Photojournal: Turkmenistan - Yacher, L. (Focus on Geography, 2006)
Keywords: Asia; Eurasia; Turkmenistan; West Asia; dept.egm; geographical research

Multifaceted NOS instruction: Contextualizing nature of science with documentary films - Bloom, M.; Binns, I.C.; Koehler, C. (International Journal of Environmental and Science Education, 2015)
This research focuses on inservice science teachers’ conceptions of nature of science (NOS) before and after a two-week intensive summer professional development (PD). The PD combined traditional explicit NOS instruction, numerous interactive interventions that highlighted NOS aspects, along with documentary films that portrayed NOS in context of authentic scientific discovery. Reflective dialogue was used throughout the professional development to encourage constructivist learning. The PD addressed seven commonly held NOS tenets that are deemed significant to K-12 science teachers. Finally, qualitative methodologies were used to analyze the Views of Nature of Science Questionnaire (VNOS-D) and the associated interview data to explore subtleties within each NOS tenet and to gain a richer understanding of how the teachers’ NOS understanding differed before and after the PD. © 2015 by iSER, International Society of Educational Research.
Keywords: Contextualized instruction; Nature of science; Professional development; dept.egm; ⚠️ Invalid DOI

Observations of the Influence of Regional Beach Dynamics on the Impacts of Storm Waves on the Connecticut Coast During Hurricanes Irene and Sandy - Tait, James F.; Ferrand, Ezgi Akpinar (Learning from the Impacts of Superstorm Sandy, 2015)
The Connecticut shoreline is one of the most intensively developed in the country. In many locations, development has relied on the buffering capacity of broad beaches for protection against storms. Much of this development is at risk due to an insufficient understanding of regional beach dynamics. The coast is commonly regarded as “protected” by the presence of Long Island. Nonetheless, Irene and Sandy imposed significant property losses on coastal cities. The most severe damages were due to wave impact in areas with narrow beaches. Small differences (as little as 21 m) in beach width proved to be significant during these storms. Sheltering by Long Island does not prevent coastal erosion during local storms. In the long run, it does prevent the rebuilding of the beach during fair weather by limiting the energy available for shoreward transport. This dynamic makes the beaches naturally erosive and their buffering capacity transient at best.
Keywords: Beach erosion; Beaches; Buffering capacities; Coastal cities; Coastal erosion; Connecticut beach dynamics; Dynamics; Energy asymmetry; Erosion; Fair weather; Hurricane Irene; Hurricane Sandy; Hurricanes; Property loss; Storm wave impacts; Storm waves; Storms; Water waves; beach erosion; dept.egm; energy asymmetry; faculty_collection; storm wave impacts

The emergence of stem - Koehler, C.; Binns, I.C.; Bloom, M.A. (STEM Road Map: A Framework for Integrated STEM Education, 2015)
Keywords: dept.egm

The stem road map for grades k-2 - Koehler, C.; Bloom, M.A.; Milner, A.R. (STEM Road Map: A Framework for Integrated STEM Education, 2015)
Keywords: dept.egm

The Kyrgyz Republic,1 central Asia, and daily life engagement - Yacher, L. (Arab World Geographer, 2016)
Keywords: Central Asia; Kyrgyzstan; dept.egm; geographical thought; life satisfaction; perception; ⛔ No DOI found

Urban food production limits and the viability of community gardens: The case of hartford, connecticut - Heidkamp, C.P.; Russell, S.E.; Sloan, M. (Local Food Systems in Old Industrial Regions: Concepts, Spatial Context, and Local Practices, 2012)
Hartford, the state capital of Connecticut, is a typical example of a former manufacturing oriented1 industrial city and, like much of the urban northeastern United States, has gone through a period of economic deindustrialization and consequent urban decay. Since the departure of the manufacturing base, Hartford has refocused its economic development on the service economy, and first and foremost, the insurance industry. The city even proclaims itself the “insurance capital of the world.” Yet, even though the insurance industry as well as other service oriented development strategies (a new convention center, science museum, and retail developments) have been quite successful in fostering economic activity and attracting employees (mostly residents of the surrounding suburbs commuting into white collar jobs), the spatial manifestations of deindustrialization are still visible and persistent in the physical as well as the social fabric of the city. © 2012 Neil Reid, Jay D. Gatrell and Paula S. Ross All rights reserved.
Keywords: dept.egm

Introduction: Sustainability in the coastal zone - Heidkamp, C.P.; Morrissey, J. (Towards Coast. Resil. and Sustainability, 2018)
Coastal areas provide many co-benefits associated with their natural infrastructure, facilitating activities such as fishing, industry, tourism and transportation, for instance (Barragán & de Andrés, 2015; Sutton-Grier, Wowk & Bamford, 2015). Despite occupying a relatively small percentage of the Earth's land surface, the value of the ecosystems’ services of coastal areas is more than one-third of the total for the globe (Barbier et al., 2011; Barragán & de Andrés, 2015). However, while the goods and services provided by coastal ecosystems are essential for economic and social well-being (Mavrommati, Bithas & Panayiotidis, 2013), coastal ecosystems are increasingly at risk. As a direct result of intensive resource use and of concentrations of population, coastal ecosystems increasingly demonstrate direct and adverse impacts of human activities (Swaney et al., 2012). Increasing population growth, movement of populations towards the coast and the increase in coastal development have led to an increase in pressure on, and degradation of, coastal ecosystems (Duxbury & Dickinson, 2007). For large coastal cities, interactions between human activities and coastal systems are intensified due to population density effects and associated economic activities (Mavrommati et al., 2013). In many parts of the world, coastal natural habitats are declining and overexploited coastal resources are dwindling, with associated impacts on ecosystems and on the livelihoods dependent on these (Mee, 2012). © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Coastal development; Coastal ecosystems; Coastal resources; Coastal zones; Economic activities; Economics; Ecosystems; Increase in pressure; Population densities; Population growth; Population statistics; Social well-being; dept.egm

Testate amoebae of peru: Filling the gap in the Neotropics - Bobrov, A.; Mazei, Y.; Buyvolova, A.; Yacher, L. (Revista de Biologia Tropical, 2019)
Testate amoebae diversity from 28 surface (0-3 cm depth) soil samples found near Cuzco (6 samples), in Machu Piсchu (17 samples), in Aguas Calientes (5 samples), and one bottom sediment sample from the Lake Titicaca near Puno were collected during March of 2016 were analyzed. The 144 testate amoebae species and infra-specific taxa belonging to 27 genera were identified. Nineteen amoebae have not been identified to species level and likely represent new taxa. Species richness varied from one to 54 taxa per sample. The highest diversity was found in rainforests followed by those in meadows and agave habitats. The only bottom sample from Lake Titicaca has yielded two hydrobiont species from the genus Difflugia. In the course of the study, several rare species with limited geographical distribution were observed, namely Centropyxis castaneus, C. compressa, C. deflandriana, C. latideflandriana, C. cf. ohridensis, C. cf. ovoides, C. cf. pannosus, C. stenodeflandriana, Cyclopyxis plana, C. profundistoma, Apodera vas, Argynnia retorta, A. spicata, Certesella certesi, Trachelcorythion pulchellum. Our study fills a geographical gap in the distribution of some flagship species with restricted geographic distribution, e.g. Apodera vas and Certesella certesi in Peru. The results illustrate the continuity of expansion species along the Pacific coast. © 2019 by Revista de Biologia Tropical. All rights reserved.
Keywords: Biodiversity; Biogeography; Mountain rainforest; Peru; Protista; dept.egm; peer-reviewed; ⛔ No DOI found

The Cold Summer of 1816 - Hoyt, J.B. (Annals of the Association of American Geographers, 1958)
Keywords: Connecticut; Farm life; History; History; Cold waves (Meteorology); History; Summer; History; Weather; dept.egm; dept.nhstc; faculty_collection

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed

Improving NGSS focused model-based learning curriculum through the examination of students’ experiences and iterated models - Park, Byung-Yeol; Campbell, Todd; Kelly, Miriah Russo; Gray, Ron; Arnold, Chester; Chadwick, Cary; Cisneros, Laura M.; Dickson, David; Moss, David M.; Rodriguez, Laura; Volin, John C.; Willig, Michael R. (Research in Science & Technological Education, 2021)
Background: It is crucial to support students in better understanding water and sustainability issues because water plays a vital role in maintaining global ecosystems, including human life. A wide range of curricular and instructional supports like those embodied in model-based learning (MBL) are necessary for teachers to engage students in the core epistemic commitments of the Next-Generation Science Standards (NGSS). Purpose: The main purpose of this study is to inform theory about students’ early attempts to engage in the complex kinds of sensemaking experiences inherent in the Framework for K-12 Science Education and the NGSS. Sample: Data for this study was collected from 74 10th grade students in a high school in the Northwest region of the New England state. Design and Methods: An explanatory sequential mixed-method research design was used to examine students’ learning outcomes, and to better understand these outcomes in connection to their experiences engaging in modeling in the MBL curriculum unit. Results: The results indicated that students’ model scores, the number of concepts in models, and the coherence and sophistication of models improved between their initial and final models. Additionally, the following patterns emerged related to ways in which students engaged in the practice of modeling: (1) students attempted to directly represent what they observed, (2) they struggled to pictorially express complex patterns or mechanisms, and (3) students experienced difficulties representing models from a diverse range of perspectives. Conclusion: The patterns identified across student models, as well as their reports of experiences related to the MBL unit implementation, provided insight into student experiences with models, while also providing meaningful implications for the refinement of the MBL curriculum unit investigated in this research specifically, while informing approaches MBL curricular units aimed at supporting NGSS implementation efforts more generally. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.egm; peer-reviewed

Who responds to health, environmental, and economic information about local food? Evidence from Connecticut seafood consumers - Tian, Yixing; Croog, Rose; Bovay, John; Concepcion, Anoushka; Getchis, Tessa; Kelly, Miriah Russo (Aquaculture Economics & Management, 2021)
We designed and implemented a discrete choice experiment to assess how information about the health, environmental, and economic benefits of locally produced aquaculture products affect Connecticut consumers’ willingness to pay (WTP) for products produced in the state, as compared with products from another state or another country. We find that information about local economic benefits tended to increase WTP for Connecticut-grown and -raised products, whereas information about health, safety, and the environment tended to decrease WTP for products from other regions. We also explore heterogeneous effects of the information treatments by respondent gender, education, and income. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.egm; peer-reviewed

Enacting a just and sustainable blue economy through transdisciplinary action research - Heidkamp, C. Patrick; Garland, Michaela; Krak, Louie (The Geographical Journal, 2021)
To enact a just and sustainable blue economy, one must consider all the actors involved in its shaping. This paper argues that a quintuple helix approach to stakeholder engagement – involving government, academia, the business community, and civil society – and an inclusive transdisciplinary action research (TAR) methodology are promising avenues with which to do so. Embracing critical pragmatism as a foundational framework, key ideas from three strands of research are consolidated: (1) the recent work on the geographical dimension of socio-technical sustainability transitions; (2) the literature on just sustainabilities and just transition; and (3) action research and transdisciplinary approaches to problem solving. This allows for the reimagination of a common future for the blue economy that is developed through a different kind of democratic process driven and informed by co-learning, and shared experiences. By adopting a transdisciplinary action research approach, actors from different disciplines and spheres of experience can gain a better mutual understanding and find commonality through the open door of collaboration. The theoretical argument presented in this paper is illustrated by a vignette of an ongoing TAR project at Southern Connecticut State University, which outlines the challenges and opportunities inherent to implementing a TAR approach. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2021 The Authors. The Geographical Journal published by John Wiley & Sons Ltd on behalf of Royal Geographical Society (with the Institute of British Geographers)
Keywords: dept.egm; peer-reviewed

Metabolic response to temperature stress in the Colombian freshwater crab Neostrengeria macropa (H. Milne Edwards, 1853) (Decapoda: Brachyura: Pseudothelphusidae) - Hudson, D.M. (Journal of Crustacean Biology, 2021)
Freshwater crustaceans are distributed throughout the montane and lowland areas of Colombia, and are therefore a useful indicator group for how aquatic species will respond to climate change. As such, metabolic determination of physiological performance was evaluated for the Colombian pseudothelphusid crab, Neostrengeria macropa (H. Milne Edwards, 1853), over a temperature range inclusive of current temperatures and those predicted by future scenarios in the plateau around the city of Bogotá, namely from 8 °C to 30 °C. The performance results mostly aligned with previous exploratory behavioral determination of the ideal temperature range in the same species, although the metabolism increased at the highest temperature treatments, a point when exploratory behavior declined. These results indicate that this species of montane crab behaviorally compensates for increased thermal stress by decreasing its physical activity, which could have negative predator-prey consequences with changes to community structure as different species undergo climate-mediated geographic range shifts in the region. As this species is endemic to the plateau surrounding Bogotá, it also experiences a number of other stressors to its survival, including infrastructure development and invasive species. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of The Crustacean Society. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: dept.egm; peer-reviewed

Assessing the resiliency of salt marshes under increasing nitrogen loading - Crosby, Sarah C.; Spiller, Nicole C.; Healy, Devan S.; Brideau, Lauren; Stewart, Luke M.; Vaudrey, Jamie M.P.; Tietz, Kasey E.; Fraboni, Peter J. (Estuaries and Coasts, 2021)
Understanding the threat to ecosystems from excess nitrogen in coastal waters is a priority issue in scientific research and natural resource management. Previous field studies have demonstrated that high nitrogen loading can decrease the health and resiliency of salt marshes through shifting biomass allocation, increasing decomposition, and causing creek bank instability, all of which can lead to increased marsh loss with sea-level rise. However, other studies have shown relatively little impact of increasing nitrogen on the structure and function of these systems. Due to the long history of eutrophication in Long Island Sound, aggressive nitrogen reduction strategies have been enacted in this region, but detrimental nutrient inputs persist at variable levels throughout the watershed. Here, the extent of nitrogen-linked salt marsh change under varying levels of nutrient stress was measured, testing the hypothesis that salt marsh resilience (as measured by Spartina alterniflora belowground biomass and marsh edge stability) decreases with increasing nitrogen loading. S. alterniflora growth (stem height, stem density, and biomass) and within-marsh creek area were quantified in 10 salt marshes along a nitrogen-loading gradient. Increasing nitrogen loading showed a significant negative relationship with dead belowground biomass in S. alterniflora; the loss of this belowground biomass in higher nitrogen systems may decrease salt marshes’ ability to keep pace with sea-level rise. Neither shifts in live biomass allocation nor a positive relationship between aboveground biomass or stem height and increasing nitrogen was observed that might promote additional sediment capture, but higher stem density could play a role in promoting sedimentation on the marsh surface in more sediment-rich systems. Aerial photography analysis revealed marsh creek expansion since 1934 at 90% of the marshes studied, but unlike findings from prior experimental enrichment studies, the rate of marsh loss did not increase with increasing nitrogen loading. Given the importance of these ecosystems and the potential of nitrogen to decrease their resiliency, understanding the impacts of eutrophication on salt marshes is critical. However, these results show that the relative importance of nitrogen in driving salt marsh loss in Long Island Sound may be less than studies from other regions have suggested. © 2021, Coastal and Estuarine Research Federation.
Keywords: Spartina alterniflora; dept.egm; peer-reviewed

Affordability, security, sustainability? Grassroots community energy visions from Liverpool, United Kingdom - Morrissey, J.; Schwaller, E.; Dickson, D.; Axon, S. (Energy Research & Social Science, 2020)
Envisioning societal futures for systemic low carbon transition is key to supporting the emergence of new configurations of the energy system. Such visions or ‘imaginaries’ facilitate wider societal support for system change. Given the urgency of the decarbonisation agenda, societal understandings of transitions processes and community ideas and visions about pathways for change assume a key role. The paper addresses an important gap in knowledge of place-based visions of energy system transition by soliciting views of community residents through a survey instrument, on what their perspectives on energy transition are. A case-study of Liverpool UK is presented, conducted as part of the EU Horizon 2020 ENTRUST project. Through a cluster analysis approach of study respondent perspectives, this study identities 4 distinct energy visions: (1) Community Affordability; (2) The Centre Ground; (3) Security First; and (4) Green Affordability. Identified visions present different perspectives on how energy is framed, with each vision characterised by distinct preferences on the extent to which stakeholder groups may influence the energy system as well as different views on the role of specific energy generation methods. Further, visions differ on the role of different actors and institutions in the energy transition. Identified energy visions provide insight into the ways in which grassroots communities consider how the energy system should transition in the coming years. The study contributes to understanding of spatially-situated and socially differentiated views of energy system transition, providing insight into contrasting viewpoints on current and future energy system priorities of residents of Liverpool, UK. © 2020 Elsevier Ltd
Keywords: Community; Energy visions; Energy-system; Grassroots; Low carbon transition; dept.egm; peer-reviewed

Contextualizing climate justice activism: Knowledge, emotions, motivations, and actions among climate strikers in six cities - Martiskainen, Mari; Axon, Stephen; Sovacool, Benjamin K.; Sareen, Siddharth; Del Rio, Dylan Furszyfer; Axon, Kayleigh (Global Environmental Change-Human and Policy Dimensions, 2020)
In August 2018, Swedish teenager Greta Thunberg started to strike from school on Fridays to protest against a lack of action on the climate crisis. Her actions sparked a historically large youth movement, leading to a series of school strikes across the world. Over the course of one week in September 2019, striking school children, students and other grassroots movements, such as Extinction Rebellion, called for everyone to participate in a global Climate Strike. This paper is based on comparative research with climate protesters in six cities: Brighton and London (United Kingdom), Montreal (Canada), New Haven and New York (USA), and Stavanger (Norway). Based on original interviews with 64 protesters, the study examines their knowledge, emotions, motivations, and actions in relation to climate change, including any lifestyle changes they have undertaken before or after their protests. Our findings show that protesters have varying degrees of knowledge about climate change, and have taken a range of actions in their own lives to address climate change. They also manifest a wide spectrum of emotions about climate change, and different motivations for taking part in climate strikes. These features are under-studied and dynamically evolving at the present conjuncture. On this basis, we call for expanded academic attention to human, emotional, epistemic, and seemingly mundane aspects of climate protests, their structural tendencies and relational expressions, and the implications for our ability to address underlying drivers. © 2020 Elsevier Ltd
Keywords: Brighton; Brighton and Hove; Canada; Climate protests; Climate strikes; Connecticut; England; Fridays for Future; Greta; Greta Thunberg; London; London [England]; Montreal; New Haven; New York; Norway; Quebec [Canada]; Rogaland; Social activism; Social movements; Stavanger; United Kingdom; United States; action plan; climate change; dept.egm; environmental justice; knowledge; lifestyle; peer; peer-reviewed; psychology

The socio-cultural dimensions of community-based sustainability: Implications for transformational change - Axon, Stephen (Journal of Cleaner Production, 2020)
There is substantial difficulty with effectively, and meaningfully, engaging the public with community-based sustainability projects as a method to facilitate sustainable lifestyles. Individuals engage with community projects in numerous ways: cognitively (knowledge), affectively (emotions), and behaviourally (actions). One prevalent consideration that individuals consider is other peoples’ (lack of) engagement; given that the success of community-based approaches addressing climate change is dependent upon the actions, and participation, of all local residents. Findings from focus groups in seven urban communities in the UK are presented that illustrate clear elements of ‘Othering’ as part of individual engagements with community-based sustainability projects. Primarily, there is substantial consideration towards what other people within the community know, feel, and do to engage with community-based projects. Residents distinguish themselves in opposition to those they view as engaging, and not engaging, in the same way as themselves and indicate the need for equitable participation amongst all residents. These considerations have the potential to project particular barriers on wider community engagement if left to develop, cause tension, and are not resolved. Implications for participatory strategies to meaningfully and effectively engage individuals with community-based sustainability and transformational change are outlined. Insights into how considerations of ‘Othering’ can be overcome so as not to cause negative engagements with other residents and attempts to live sustainably as part of a community approach are illustrated. © 2020
Keywords: Climate change; Communities; Community based approach; Community engagement; Community project; Community-based; Community-based projects; Local residents; Othering; Public engagement; Sustainability project; Sustainability science; Sustainable development; Sustainable lifestyles; Transformational change; Transformations; Urban community; dept.egm; peer-reviewed

“I’m a bit of a waster”: Identifying the enablers of, and barriers to, sustainable food waste practices - Wakefield, Alysia; Axon, Stephen (Journal of Cleaner Production, 2020)
Food waste has become an area of increasing concern in recent years, since unsustainable food waste practices have been associated with a range of adverse environmental, economic and societal impacts. Food waste is a multi-sectoral issue and must be addressed as such, by ensuring policymakers, practitioners, and consumers are equipped with the relevant knowledge and understanding of the importance of sustainable food waste practices. By exploring current attitudes and understanding of this topic amongst consumers, a lack of education about the importance of this issue has been identified as a barrier to carrying out sustainable practices at the household level, along with excess packaging, cultural norms of overconsumption and inappropriate social marketing. In contrast, a number of enablers, including social pressures, access to appropriate facilities and encouragement from media advertisements appear to have been highly influential in infringing on the consciousness of consumers. Investigating these enablers and barriers has allowed a number of potential interventions to be identified, with the intention of addressing this issue using a multifaceted approach and encouraging society to carry out sustainable food waste practices in the future. © 2020
Keywords: Contrast media; Cultural norms; Economic and social effects; Food waste; Food waste management; Household level; Marketing; Multi-faceted approach; Policy makers; Social marketings; Social pressures; Societal impacts; Sustainable consumption; Sustainable development; Sustainable lifestyles; Sustainable practices; dept.egm; peer-reviewed

Beach morphology and nearshore processes on a sheltered beach — The case of Napatree Beach, Rhode Island - Sakalowsky, Peter P. (Marine Geology, 1975)
On the north side of Napatree Beach, short-term changes of the beach-face within the intertidal zone were studied to determine those processes most influential in causing change where nearshore processes are low in magnitude and beach changes are subtle. The data were subjected to multiple linear correlation and stepwise multiple-regression analyses. Tide level accounts for 41% of the explained variation for the relationship between the processes and beach height. Tide level is the only significant element effecting change in the beach profile. Wave height has no influence on changes in beach morphology. Significant results of beach energy associations have been obtained where low-amplitude nearshore processes are present even when beach changes are subtle. © 1975.
Keywords: dept.egm

Israel's maritime boundaries - Glassner, Martin Ira; Unger, Michael (Ocean Development and International Law, 1974)
While land boundaries have occupied the attention of Israelis since 1948 and even earlier, they have been little concerned with the sea, and the legislation concerning their maritime boundaries is vague and incomplete. In addition, since the Six Day War Israel occupies territory with several different territorial seas, resulting in a quite complex ad hoc situation. The sea is becoming more important to Israel and she is gradually turning her attention more and more to maritime matters. It would be well if an orderly system of maritime boundaries and cooperation in utilizing the resources of the sea could be arranged with her neighbors, but that seems impossible for the forseeable future. It does seem likely, however, that in connection with or shortly after the forthcoming Law of the Sea Conference, Israel will as a minimum extend her territorial sea from six miles to twelve, while stoutly maintaining the right of free transit through international straits. © 1974 Taylor & Francis Group, LLC.
Keywords: dept.egm

Robert lemoyne barrett, 1871–1969; last of the founding members of the association of american geographers1 - Martin, Geoffrey J (The Professional Geographer, 1972)
Keywords: dept.egm

Nationalism in Early American Geographies: 1784-1845 - Antonelli, Michael F. (Journal of Geography, 1970)
There existed clear demonstrations of nationalism in geography textbooks written by Americans during two significant epochs in the history of the United States. Geographies regarded the environment, people or institutions of the United States either with extreme adulation or subtle pride. They viewed the nation favorably when its strengths and weaknesses were compared to each other or to foreign elements, even when objective evidence did not support such an assessment. And, finally, they reached a host of young and impressionable Americans, and instilled in them a fervor for their country. © 1970 Taylor and Francis Group, LLC.
Keywords: dept.egm

The evolution of beersheba as an urban center1 - Berman, Mildred (Annals of The Association of American Geographers, 1965)
Beersheba has changed from a small agricultural settlement in pre-Biblical times to a city of importance in modern Israel. The wells and fertile loess soils of the Beersheba Basin have been utilized by all who have occupied the area. From 3300 B.C. to the present, Beersheba has functioned as an oasis, market town, military center, transportation node, and as a traditional gathering place for the Bedouin tribes of the Negev, Israel's southern desert. In 1900, the Ottoman Turks initiated the modern development of Beersheba. After World War I, the British administered the area as part of the Palestine Mandate. With the creation of the state of Israel in 1948, the city began to grow rapidly. In the early 1960′s, Beersheba had a population of over 52,000. It functions as the capital of a region containing over two-thirds of the national area. © 1965, Taylor & Francis Group. All rights reserved.
Keywords: dept.egm

Israel's dynamic frontier region-the negev - Berman, Mildred (Journal of Geography, 1964)
Keywords: dept.egm

Geography in Peru - Yacher, Leon (The Professional Geographer, 1989)
Keywords: dept.egm

On whittlesey, bowman and harvard - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
Keywords: dept.egm

Preston E. James, 1899–1986 - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
Keywords: dept.egm

Against presentist histories: solot's view of sauer - Speth, William W (Annals of The Association of American Geographers, 1987)
Keywords: dept.egm

The ecologic tradition in american geography 1895–1925 - Martin, Geoffrey J (Canadian Geographer, 1987)
Keywords: dept.egm

On the discrimination of Anthropo‐Geocraphies - Speth, William W (Canadian Geographer, 1987)
Keywords: dept.egm

Paradigm change: a history of geography in the United States, 1892-1925. - Martin, G.J. (National Geographic Research, 1985)
The third of 5 paradigm periods posited for the history of American geography extends from the establishment of the Committee of Ten in 1892, to the publication of Carl Sauer's 'The Morphology of Landscape' in 1925. This period witnessed the emergence of discipline and profession - an inert physiography, energized by the discipline-forming Davisian cycle of erosion, preceded the causal notion. Determinisms that gave way to studies of control, adjustment, and the geographic factor, provided a framework for the geographic philosophies of such scholars as Albert Perry Brigham, Ellsworth Huntington, and Ellen Semple. Regional delimitations of physiographic provinces and variant forms of economic geography emerged as alternatives to causality. The geography of France, Germany, and Britain afforded little support for varieties of determinism in America, and was further questioned during the 1914-1918 war years. Meanwhile, Wellington D. Jones and Carl O. Sauer developed another viewpoint, adumbrated by Sauer in a series of papers culminating in 'The Morphology of Landscape'. The locus of American geography had been moved.-Author
Keywords: dept.egm; ⛔ No DOI found

Preservation of the history of geography - Martin, G.J. (Journal of Geography, 1985)
Keywords: dept.egm

New haven, connecticut, from the air - Richason, F Benjamin; Yacher, Leon (Journal of Geography, 1981)
Keywords: dept.egm

ON AAG history - James, Preston E; Martin, Geoffrey J (The Professional Geographer, 1979)
The seventy-fifth anniversary of the Association of American Geographers is a time to celebrate. To set the tone for the anniversary meetings in Philadelphia, I asked Geoffrey Martin, Marvin Mikesell, and John Adams to discuss significant events in the AAG's past, the Association’s present state, and prospects for the future. Their presentations were made in the initial session of the meetings on Sunday evening, April 22. We are pleased to reproduce for the members of the Association the transcripts of those verbal presentations. We are indebted to each of these colleagues for the excellent start they provided for our largest-ever professional meeting.—Brian J. L. Berry, President. © 1979 by the Association of American Geographers.
Keywords: dept.egm

The emergence and development of geographic thought in new england - Martin, Geoffrey J (Economic Geography, 1998)
Some of the early settlers of New England brought with them the works and thought of European geographers, notably Ptolemy, Munster, Cluver, Carpenter, and Varenius. Beginning in the 1600s the work of British geographers Gordon and Salmon and Guthrie and Pinkerton was acknowledged, preceding that of Jedidiah Morse, “Father of American Geography.” Morse led the way for a large number of geography texts written by Americans, emphasizing North America and characterized by Varenius's special geography. Early collegiate developments in New England geography were led by Harvard and Yale universities, the College of Rhode Island (later renamed Brown University), and Dartmouth College. The 20 or so normal schools throughout New England, introduced in the middle 1800s, constituted a nursery for geographic education. Also noted are more recent college and university geography departments established throughout the region, including notably Clark University. The founding of societies and associations in New England also furthered the cause of geography.
Keywords: Geography; Harvard; History; Morse; USA, New England; Varenius; Yale; dept.egm; geographical thought; geography education; history of geography

Resolving the problems of land‐lockedness - Glassner, Martin Ira (Geopolitics, 1997)
The professional literature on land-locked states has increased substantially in the past two decades. There is now a considerable body of writings by people in many countries around the world reporting on, inquiring into or carefully analysing most aspects of land-lockedness from various disciplinai and national viewpoints. In addition, there is a roughly equally large body of material related to land-lockedness produced by the United Nations and its organs and affiliates; by other intergovernmental organisations, including many regional and subregional groups; and by private consultants and consulting firms, chiefly in the fields of economics and engineering. © 1998 Frank Cass.
Keywords: dept.egm

A response to dimitri ioannides, “Strengthening the ties between tourism and economic geography: A theoretical agenda.” - d'Hauteserre, Anne-Marie (The Professional Geographer, 1996)
Keywords: dept.egm

Book review: France's overseas frontier: Départements et territoires d'outre-mer: Robet Aldrich and John Connell, Cambridge University Press, 1992 - Glassner, Martin Ira (Political Geography, 1995)
Keywords: dept.egm

Book Review: Nauru: Environmental damage under international trusteeship: Christopher Weeramantry, Oxford University Press, Melbourne, 1992 - Glassner, Martin Ira (Political Geography, 1995)
Keywords: dept.egm

Book Review: The Dutch Caribbean: Prospects for democracy: Betty Sedoc-Dahlberg, Gordon and Breach, New York, 1990 - Glassner, Martin Ira (Political Geography, 1995)
Keywords: dept.egm

Tagging and migration of the American lobster Homarus americanus - Haakonsen, H. O.; Anoruo, A. O. (Reviews in Fisheries Science, 1994)
Three types of tags, external, internal, and sonic, have been used to study migration of the American lobster Homarus americanus. Tag loss and interpretation of returned tag data are serious problems associated with internal and external tags. Lobster tracking using sonic tags is still in the pilot stage. Lobster migration is redefined to include horizontal and vertical displacements. Depth of displacement is a more reasonable measurement of lobster migration than horizontal distance traveled. Two distinct lobster populations are discernable based on their ecological habitation and migratory behavior. Evidence in this review suggests that the deep-sea lobster migrates, whereas the coastal lobster may move within a limited range. © 1994, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Homarus americanus; coastal lobster; deep-sea lobster; dept.egm; migration

Recent contributions of the United Nations to political geography - Glassner, Martin Ira (Political Geography, 1994)
Keywords: dept.egm

Book Review: Review essay: Recent books on marine affairs - Glassner, Martin Ira (Ocean Development and International Law, 1993)
Keywords: book.review; dept.egm

Management of marine resources as a binding force in the Eastern Caribbean - Glassner, Martin Ira (Ocean & Coastal Management, 1993)
The history of the Commonwealth Caribbean is replete with failed attempts at various degrees of economic and political integration. The Caribbean Sea itself is rather poor in both living and non-living resources, and the entire region-land and water-is suffering from varying degrees of environmental degradation. This article suggests that regional co-operation in the management of marine resources, particularly in the Anglophone islands of the Eastern Caribbean, could serve as an 'engine of integration'-something previous attempts lacked. There is no assurance that such an effort would be successful, however, despite good intentions, co-operation in many areas at present and some real cultural affinities. The centrifugal forces at work here are still very powerful, including parochialism and the scarcity of resources other than sun, sand and sea. © 1993.
Keywords: Anglophone islands; Caribbean; Caribbean, (East); Centrifugal forces; Coastal engineering; Commonwealth Caribbean; Eastern caribbean; Engine of integration; Environmental degradation; Environmental impact; Laws and legislation; Management; Management of marine resources; Scarcity of resources; dept.egm; developing country; economic and political integration; economic association; environmental degradation; environmental resource management; marine resource management; marine resources; regional cooperation; resources management

Enhancing teaching excellence through a scientist-science teacher collaborative process. - Haakonsen, Harry O; Stone, A Harris; Tomala, Gail; Hageman, Susan (Journal of Science Teacher Education, 1993)
Keywords: dept.egm

Book Review: The exclusive economic zone - regime and legal nature under international-law - vicuna,fo - Glassner, Martin Ira (Marine Policy, 1991)
Keywords: dept.egm

The Age of the Arctic: Hot Conflicts and Cold Realities. By Gail Osherenko and Oran R. Young. Cambridge: Cambridge University Press, 1989. 316p. $59.50. - Glassner, Martin Ira (American Political Science Review, 1991)
Keywords: dept.egm

The law of the sea and international shipping: AngloSoviet post-UNCLOS. W.E. Butler (ed). New York, London and Rome: Oceana Publication, 1985 - Glassner, M.I. (Political Geography Quarterly, 1991)
Keywords: dept.egm

Book Review: Die seerechtliche verteilung von nutzungsrechten; rechte der binnenstaaten in der ausshliesslichen wirtschaftszone: Gerhard Hafner, Vienna and New York: Springer Verlag, 1987 - Glassner, Martin Ira (Political Geography Quarterly, 1991)
Keywords: book.review; dept.egm

The frontiers of earth — and of political geography: The sea, Antarctica and outer space - Glassner, Martin Ira (Political Geography Quarterly, 1991)
Keywords: dept.egm; ⛔ No DOI found

Book Reivew: Maritime boundaries and ocean resources: Gerald Blake (ed.), Croom Helm, Beckenham, Kent, 1987, xiii + 284 pp., £27.50 - Glassner, Martin I. (Political Geography Quarterly, 1989)
Keywords: dept.egm

Book review: International and United States documents on oceans law and policy: John Norton Moore (ed.), William S. Hein, Buffalo, NY, 1986, 5 vols., $195.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
Keywords: dept.egm

Book Review: The refugee problem on universal, regional and national level: Thesaurus Acroasium, Vol. XIII, Institute of International Public Law and International Relations of Thessaloniki, 1987, xvi + 1022pp., $150.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
Keywords: dept.egm

Book review: Geopolitics of the Caribbean: Ministates in a wider world: T.D. Anderson, Praeger, New York, 1984, xiii + 175 pp., $26.95 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
Keywords: dept.egm

Book review: National interests and the military use of space: W.J. Durch (ed.), Ballinger, Cambridge, Mass, 1984, xiv + 304 pp., $28.00 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
Keywords: dept.egm

The new political geography of the sea - Glassner, Martin Ira (Political Geography Quarterly, 1986)
The political geography of the sea may be defined as that portion of the Law of the Sea which has a spatial or territorial component, including such matters as the territorial sea and the contiguous zone, the exclusive economic zone, international straits, the regimes of islands and archipelagos, freedom of transit for land-locked states, deep seabed mining and protection and preservation of the marine environment. It also includes larger issues not formally part of the Law of the Sea, such as the links between the Law of the Sea and Antarctica, and military uses of the sea. The new Law of the Sea (hence the new political geography of the sea) is the latest stage in a long evolution traceable to the ancient Greeks and Romans but accelerating since the 17th century. The United Nations Conference on the Law of the Sea produced in 1958 four conventions essentially codifying the existing Law of the Sea, including the new continental shelf doctrine. They were followed by the 1965 UN Convention on Transit Trade of Land-locked States. All soon proved inadequate, unacceptable or obsolescent. The Third United Nations Conference on the Law of the Sea (UNCLOS III, 1973-1982) produced a new single, comprehensive convention embodying nearly all old and new aspects of the Law of the Sea. This and related matters deserve much greater attention from political geographers than they have received thus far. © 1986.
Keywords: dept.egm

Political geography of contemporary events VII: The view from the near north— South Americans view Antarctica and the Southern Ocean geopolitically - Glassner, Martin Ira (Political Geography Quarterly, 1985)
Keywords: dept.egm

The Kyrgyz Republic's Liminal Media: assessing a journalistic rite of passage - Manzella, Joseph C; Yacher, Leon (Journalism Studies, 2005)
In the Western world, the Kyrgyz Republic has been depicted as a democratic success story. Indeed, unlike other Central Asia nation states, the Kyrgyz media appears on the surface relatively free. This paper examines the Kyrgyz press in the context of journalistic ideologies, and suggests that the republic's media is going through an important transitional phase, the central stage of a journalistic rite of passage. Part of that transitional process is an ongoing ideological tug-of-war that awaits resolution. It is suggested that such resolution may occur only when the press becomes economically self-sustaining. © 2005 Taylor & Francis Group, LLC.
Keywords: Journalistic Ideologies; Kyrgyz Media; Rite of Passage; dept.egm

Citrate-mediated increase in the uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene residues by plants - White, Jason C; Kottler, Bennett D (Environmental Toxicology and Chemistry, 2002)
Experiments were conducted to determine the ability of citrate to enhance the plant uptake of weathered 2,2-bis(p-chlorophenyl)1,1-dichloroethylene (p, p′-DDE) from soil. Plots containing three rows of clover, mustard, hairy vetch, or rye grass were constructed in soils containing p, p′-DDE. On 11 occasions, the rows of each crop received water or sodium citrate (0.005 or 0.05 M). For each crop, there were significant reductions in p, p′-DDE concentration in the soil fractions (near root and rhizosphere) closely associated with the plant versus bulk soil. The roots of each crop accumulated 2 to 5 times more of the weathered contaminant (dry wt) than present in the bulk soil. Citrate (0.05 M) increased the concentration of p, p′-DDE in the roots of clover, mustard, and hairy vetch by 39% compared with vegetation that received water. In batch desorption studies, the release of weathered p, p′-DDE was significantly greater in the presence of 0.05 M citrate than in water. Citrate increased the extracted aqueous concentrations of five metal ions (Al, Fe, Ca, K, Mn) from soil by five- to 23-fold over distilled water. We hypothesize that citrate physically disrupts the soil through chelation of structural metal ions and release of bound humic material, facilitating p, p′-DDE availability and uptake by plants.
Keywords: 1,1 dichloro 2,2 bis(4 chlorophenyl)ethylene; Bioavailability; Biodegradation, Environmental; Brassica; Chelating Agents; Chelation; Citric Acid; Dichlorodiphenyl Dichloroethylene; Drug Interactions; Extraction; Humic Substances; Impurities; Insecticides; Ions; Metals; Organic compounds; Phytoremediation; Plants; Plants (botany); Secale cereale; Sequestration; Soil Pollutants; Soil fractions; Soil pollution; Tissue Distribution; Trifolium; Vegetation; Vicia; Vicia villosa; Water; aluminum; aqueous solution; article; bioavailability; biological uptake; bioremediation; calcium; chelation; citric acid; clover; concentration (parameters); dept.egm; desorption; iron; manganese; metal ion; nonhuman; phytoremediation; plant; plant root; potassium; priority journal; rhizosphere; rye; soil pollution; water

Influence of soil moisture on the sequestration of organic compounds in soil. - Kottler, Bennett D.; White, Jason C.; Kelsey, Jason W. (Chemosphere, 2001)
A study was conducted as a part of continuing investigation of the effect of soil moisture on the sequestration of organic compounds aged in the soil. Here, experiments focused on the effects of moisture changes within the soil before, during, and after contaminant addition. The extractability of aged (68 d) phenanthrene was greater from soil that had been subjected to wetting and drying cycles prior to solute addition as compared to soil initially maintained at constant moisture. The recovery of phenanthrene added to moist soil was increased relative to extractability from soil that was air-dried at the time of the contaminant addition. Repeated wetting and drying of soil after the addition of atrazine or phenanthrene resulted in decreased extractability of the compounds as compared to samples maintained at constant moisture. A method for rapidly sequestering contaminants is proposed and may be useful in limiting the time required for laboratory studies involving "aged" contaminants. These data build upon the findings of earlier work from our laboratory and indicate that changes in the moisture conditions of soil can affect the availability of sequestered contaminants possibly through alterations in the structure of the natural solid. © 2001 Elsevier Science Ltd.
Keywords: Aging; Atrazine; Bioavailability; Biological Availability; Extraction; Organic Chemicals; Phenanthrene; Phenanthrenes; Soil; Soil Pollutants; Water; article; atrazine; bioavailability; chemical structure; dept.egm; extraction; leaching; moisture; organic compound; phenanthrene; phenanthrene derivative; soil moisture; soil pollution; solid state; wetting-drying cycle

Lessons in managed destination competitiveness: the case of Foxwoods casino resort. - d'Hauteserre, Anne-Marie (Tourism Management, 2000)
Foxwoods, which started as a Binge gaming facility, has become the largest casino in the western world. It is one of the most competitive tourist destinations in the world and can teach a few lessons about managing competitiveness. The visionary entrepreneurial activity, strategic management decisions of its owners and the Mashantucket Pequots are the reasons for its existence and its success, not some circumstantial fluke. The Pequots understood the destination's potential initial advantage. They then sought to avoid that Foxwoods casino and resort slip into McGambling or wither in the face of increasing competition for the entertainment/leisure dollar in the eastern United States by modifying its market positioning. They are now nudging it toward a broadly diversified base of entertainment. All along they empowered their employees to support their clear mission for the resort. Part of their strategy is to transform southeastern Connecticut into a synergistic tourist destination for their and the region's benefit. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: Competitiveness; Connecticut; Foxwoods; Gam(bl)ing; Strategic planning; Tourist destination; United States; competitiveness; dept.egm; gambling; management practice; recreational activity; tourism economics

A land use model of the effects of eco-labeling in coffee markets - Heidkamp, Patrick; Hanink, Dean M.; Cromley, Robert G. (Annals of Regional Science, 2008)
International non-profit organizations have started to implement eco-labeling for credence attributes programs aimed to inform consumers about environmentally sound or “sustainable” production standards for various products. Using coffee labeled as “shade grown” or “bird friendly” as an example, this paper describes the impact such labeling programs may have on local land use patterns in coffee producing regions. Shade grown coffee farms should provide a variety of external benefits, including the preservation of biodiversity, carbon sequestration, the prevention of soil erosion and aquifer recharge. Those externalities, however, are not expected to have observable land use impacts unless they are capitalized in the coffee market. The prospect of market capitalization of externalities suggests the extension of the conventional von Thunen model to the calculation of social location rent. Using the maximization of social location rent as a criterion allows the externality effect to play a direct role in market-based land use allocation of land between eco-labeled shade grown coffee production and other activities.
Keywords: Aves; agricultural market; coffee; crop production; dept.egm; ecolabeling; land use; modeling

Offshore threats: Liquefied natural gas, terrorism, and environmental debate in Connecticut - Harrison, Blake (Annals of The Association of American Geographers, 2008)
Broadwater Energy is one of a number of recent proposals to construct a liquefied natural gas facility along the East Coast of the United States. The proposal calls for the construction of an import and regasification terminal in Long Island Sound, roughly halfway between the states of New York and Connecticut. First made public in 2004 by its sponsors, TransCanada and Shell, the Broadwater proposal has inspired opposition from a range of interest groups. An examination of the Broadwater debate with a focus on arguments made by Connecticut residents in the months leading up to the release in late 2006 of the proposal's Draft Environmental Impact Statement reveals explicit and implicit points of overlap between concerns about the facility's environmental impacts and concerns about its status as a potential terrorist target. Discussions about terrorism deployed in the Broadwater debate have initiated and informed a politics of scale through which themes common to environmental debates have been transformed. This transformation, in turn, highlights the discursive and material influence of terrorism in contemporary U.S. society. Concerns about terrorist attacks have been deployed by activists to enhance the strength of an otherwise environmental debate and, in the process, those concerns have developed the potential to shape land use policy in Long Island Sound. Key Words: environmentalism, liquefied natural gas, Long Island Sound, scale, terrorism.
Keywords: Connecticut; Environmentalism; Liquefied natural gas; Long Island Sound; North America; Scale; Terrorism; United States; container terminal; dept.egm; environmental impact; environmental policy; environmentalism; land use planning; liquefied natural gas; offshore engineering; terrorism

Five new species of jaltomata (solanaceae) from cajamarca, peru - Mione, Thomas; Leiva, G Segundo; Yacher, Leon (Novon, 2007)
Five new suffrutescent to shrubby Jaltomata Schlechtendal species (Solanaceae) of the department of Cajamarca, Peru, are described and illustrated, Jaltomata contumacensis S. Leiva & Mione has a light green, urceolate-tubular corolla and grows in the province of Contumazá between 2530 and 3000 m; J. lanata S. Leiva & Mione has a whitish purple to pale purple, short-tubular corolla and grows in the province of San Pablo between 1850 and 2400 m; J. leivae Mione has a red-violet, urceolate corolla containing red nectar and grows in the province of Contumazá between 2560 and 2650 m; J. oppositifolia S. Leiva & Mione bas a white, broadly infundibular to rotate corolla and grows in province Chota between 2250 and 3090 m; and J. yacheri Mione & S. Leiva has a blue-purple, urceolate corolla and grows in province Hualgayoc at 3460 m. The fruits of two of these species are eaten by people.
Keywords: Edible fruit; Jaltomata; Magnoliophyta; Red nectar; Solanaceae; dept.egm

Shopping to save: green consumerism and the struggle for northern Maine - Harrison, Blake (Cultural Geographies, 2006)
Between 2001 and 2003, Roxanne Quimby - then the sole owner of a natural personal-care products company named Burt's Bees - invested millions of dollars of her company's profits in tens of thousands of acres of forestland in northern Maine. Her intention was to donate that land to the United States government on behalf of a controversial national park proposed for the region - the Maine Woods National Park. Quimby's actions set off sharp debates between policy makers, environmentalists and residents of northern Maine. As this article suggests, those debates were informed in part by their association with green consumerism. When consumers purchase `environmentally friendly' products like those made by Burt's Bees, they typically envision their actions as having positive consequences for places associated directly with the production and consumption of that product. In this case, however, profits from a green consumer product were reinvested outside its immediate commodity chain, thereby implicating green-consumer decisions in a politics of identity and landscape control beyond that product's lifecycle. This paper explores that process, suggesting that even the most well-intended consumer choices can carry social and environmental consequences into new and perhaps unexpected terrain. When we shop to save, we can never be quite certain of what it is that we are saving.
Keywords: Apoidea; Maine; North America; United States; consumption behavior; dept.egm; profitability

Maynard weston dow (1929–2011) and “Geographers on film” - Martin, Geoffrey J (Annals of The Association of American Geographers, 2013)
Keywords: art; dept.egm

American Geography and Geographers: Toward Geographical Science - Martin, Geoffrey J. (Oxford University Press, 2014)
The rise of American geography as a distinctive science in the United States straddles the 19th and 20th centuries, extending from the post-Civil war period to 1970. American Geography and Geographers: Toward Geographic Science is the first book to thoroughly and richly explicate this history. Its author, Geoffrey J. Martin, the foremost historian on the subject and official archivist of the Association of American Geographers, amassed a wealth of primary sources from archives worldwide, which enable him to chart the evolution of American geography with unprecedented detail and context. From the initial influence of the German school to the emergence of Geography as a unique discipline in American universities and thereafter, Martin clarifies the what, how and when of each advancement. Expansive discussion of the arguments made, controversies ignited and research voyages move hand in hand with the principals who originated and animated them: Davis, Jefferson, Huntington, Bowman, Johnson,, Sauer, Hartshorne, and many more. From their grasp of local, regional, global and cultural phenomena, geographers also played pivotal roles in world historical events, including the two world wars and their treaties, as the US became the dominant global power. American Geography and Geographers: Toward Geographical Science is a conclusive study of the birth and maturation of the science. It will be of interest to geographers, teachers and students of geography, and all those compelled by the story of American Geography and those who founded and developed it.
Keywords: Geography; History; History; Geographers; History; United States; Study and teaching; Study and teaching (Higher); United States; dept.egm; faculty_collection

Residential perspectives: the value of Floodplain‐ buyout open space - Zavar, Elyse (Geographical Review, 2015)
This mixed-methods case study identifies how floodplain property acquisitiona buyoutimpacts an urban environment at the neighborhood scale while considering the role of individual residents in formal and informal land-use decision making. In floodplain buyouts, the reopening of urban space is enabled by federal structural drivers, primarily Federal Emergency Management Agency (FEMA), but it is repurposed as a cultural landscape constructed and produced by individuals. This research explores how residents perceive and ascribe values to the buyout landscape in Lexington, Kentucky. Enabled by federal funds, but left largely to their own devices, residents in Lexington adopted uses, ascribed values, and produced their own land-use norms in each buyout neighborhood.
Keywords: dept.egm; floodplain; land management; land value; peer-reviewed; property acquisition

The role of magnetic agents in shaping post-disaster land use - Zavar, Elyse (Land Use Policy, 2016)
Three neighborhoods in Lexington, Kentucky, share a common flood history, including property acquisitions, as a means to mitigate against flooding; yet, the interactions of residents with the buyout landscapes vary significantly among the neighborhoods. Although the same institutions and structural controls implemented flood buyout programs in all three neighborhoods, semi-structured interviews illustrate that differing perspectives, personalities, and neighborhood politics shaped unique identities and land uses for the acquired properties in each neighborhood. Varying levels of resident engagement with the buyout landscape resulted in a range of attitudes towards hazard preparation, management, and mitigation, thus leaving some neighborhoods more resilient to future flooding than others. This study explores key residents, termed magnetic agents, who drove neighborhood civic action and land uses on the open space created through floodplain property acquisition. This research indicates magnetic agents can serve as important partners for local governments and non-governmental organizations (NGOs) in building community-based projects aimed at reducing vulnerability to flood events and instituting high utility land uses on floodplain buyout open space.(C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Agency; Floodplain buyout; Kentucky; Land management; Lexington; Resiliency; United States; dept.egm; flooding; floodplain; hazard management; land management; land use planning; neighborhood; open space

The Modifiable Conceptual Unit Problem demonstrated using pollen and seed dispersal - Miller, Matthew D (Global Ecology and Conservation, 2016)
The Modifiable Areal Unit Problem (MAUP) is a famous issue in spatial analysis that states the output of a spatial analysis is influenced by the spatial extent of the units used in the analysis. This study demonstrates that the MAUP is accompanied with another intractable spatial issue in spatial modeling; the Modifiable Conceptual Unit Problem (MCUP). The MCUP states that the conceptualization of spatial processes impacts the output of spatial analysis and occurs when a model with one spatial dimension is applied to a spatial model with more than one spatial dimension. This study demonstrates the MCUP by developing three conceptual models of dispersal and showing how they produce different results even when given the same initial dispersal curves and areal units. Three conceptual models of dispersal (sum of curve points model, area of distance range model, and the volume of distance range model) are described and applied to a grid landscape with a single point of dispersal and a grid landscape with multiple points of dispersal. A Geographic Information System (GIS) is used to evaluate how the models differ in their distribution of pollen or seeds across the landscapes. The three models of dispersal are each valid conceptualizations of the dispersal process, but when given the same dispersal curve parameters, they produce different distributions of dispersed items across grid landscapes. The sum of curve points model is the least complicated model because it only uses a few points from the defined dispersal curve. The area of distance range model uses the entire dispersal curve, but is based on a single dimension of space and thus conceptually abstracted from the grid landscape. The volume of distance range model uses the two spatial dimensions present in the grid landscape and thus is the most conceptually sound model of the three. The underlying conceptualization of the dispersal process can impact the results of dispersal models. Applying dispersal curves with one spatial dimension to grids with two spatial dimensions makes inherent assumptions about the conceptualization of dispersal. This study highlights the necessity of researchers to declare their conceptual models of dispersal when applying modeled dispersal curves to grid landscapes. © 2016 The Author.
Keywords: Conceptual; Dispersal; Grid; MAUP; Pollen; Spatial; dept.egm

Land use change on US floodplain buyout sites, 1990-2000 - Zavar, Elyse; Hagelman, III, Ronald R. (Disaster Prevention and Management, 2016)
Purpose - The Federal Emergency Management Agency provides guidelines for the management of open space created through property acquisition (buyouts); however, land use decisions are primarily left to local governments manifesting in a variety of uses. The purpose of this paper is to provide a land use assessment of buyout sites, to describe the changes in those uses that have occurred during a ten-year period from 1990 to 2000, and to offer an assessment of management approaches employed across these sites. Design/methodology/approach - Using a mixed-methods approach consisting of a land use classification survey and a semi-structured questionnaire of floodplain managers, this study explores the land use trends at buyout sites, diverse approaches local governments take in managing the open spaces created through floodplain buyout programs, and the successes and challenges communities face in open space management. Findings - Results indicate strong support from floodplain managers for property acquisition and several cases emerged where communities put their newly acquired public land to creative uses. However, the opportunity to leverage these properties for greater public values is largely being missed, primarily because of limited funding. Practical implications - The analysis indicates strong support among floodplain managers for the buyout approach; however, additional resource-sharing and funding opportunities are needed to increase the utility of buyout properties. Originality/value - By evaluating the long-term management strategies floodplain managers utilize on buyout sites, this study adds to an underrepresented area of scholarship and is of value to practitioners, government officials, and academics.
Keywords: Buyout; Disaster mitigation; Floodplain management; Land use; dept.egm

Rainwater Harvesting as an Effective Climate Change Adaptation Strategy in Rural and Urban Settings - Ferrand, Ezgi Akpinar (Managing Water Resources under Climate Uncertainty: Examples from Asia, Europe, Latin America, and Australia, 2015)
Human societies are known for their resilience and ability to adapt to short- and long-term environmental change. Despite their pragmatism and adaptability, humans could be forced to move and/or seek better conditions for survival, especially when climate change and water availability are at issue. This chapter provides case studies on easy-to-adopt rainwater harvesting applications as effective climate change adaptation strategies in rural and urban settings to increase human resiliency.
Keywords: Climate Change Adaptation; Climate change adaptation; Rainwater Harvesting; Rainwater harvesting; Urban and Rural Settings; Urban and rural settings; dept.egm

Two new Peruvian species of Jaltomata (Solanaceae, Solaneae) with red floral nectar - Mione, Thomas; González, Segundo Leiva; Yacher, Leon (Brittonia, 2014)
Two new Jaltomata species (Solanaceae) of Peru that produce red floral nectar are described. Jaltomata neei of Department Cajamarca has 1–4 flowers per inflorescence, the campanulate corolla is green and then changes to blue, corolla lobes (5) and lobules (5) are equally prominent, a corona is lacking, five radial staminal-corolla thickenings create nectar troughs between, and the stigma is capitate. Jaltomata quipuscoae of Department Arequipa has solitary flowers, a purple, broadly crateriform, 5-lobed corolla, a corona on which nectar pools, a punctiform stigma, lacks corolla thickenings, and the mature fruit is whitish. Photographs, illustrations and tables are included that allow comparison with closely related species. © 2014, The New York Botanical Garden.
Keywords: Arequipa; Cajamarca; Jaltomata neei; Jaltomata quipuscoae; Peru; corolla color change; corona; dept.egm; lomas; protogyny; red nectar

Metals, Organic Compounds, and Nutrients in Long Island Sound: Sources, Magnitudes, Trends, and Impacts - Varekamp, Johan C.; McElroy, Anne E.; Mullaney, John R.; Breslin, Vincent T. (Long Island Sound: Prospects for the Urban Sea, 2014)
Long Island Sound (LIS) is a relatively shallow estuary with a mean depth of 20 m (maximum depth 49 m) and a unique hydrology and history of pollutant loading. These factors have contributed to a wide variety of contamination problems in its muddy sediments, aquatic life, and water column. The LIS sediments are contaminated with toxic compounds and elements related to past and present wastewater discharges and runoff. These include nonpoint and stormwater runoff and groundwater discharges, whose character has changed over the years along with the evolution of its watershed and industrial history. Major impacts have resulted from the copious amounts of nutrients discharged into LIS through atmospheric deposition, domestic and industrial waste water flows, fertilizer releases, and urban runoff. All these sources and their effects are in essence the result of human presence and activities in the watershed, and the severity of pollutant loading and their impacts generally scales with total population in the watersheds surrounding LIS. Environmental legislation passed since the mid-to-late 1900s (e.g., Clean Air Act, Clean Water Act) has had a beneficial effect, however, and contaminant loadings for many toxic organic and inorganic chemicals and nutrients have diminished over the last few decades (O’Shea and Brosnan 2000; Trench et al. 2012; O’Connor and Lauenstein 2006; USEPA 2007). Major strides have been made in reducing the inflow of nutrients into LIS, but cultural eutrophication is still an ongoing problem and nutrient control efforts will need to continue. Nonetheless, LIS is still a heavily human impacted estuary (an “Urban Estuary,” as described for San Francisco Bay by Conomos 1979), and severe changes in water quality and sediment toxicity as well as ecosystem shifts have occurred since the European colonization in the early 1600s (Koppelman et al., 1976). The Sound has seen the most severe environmental changes over the last 400 years during its 10,000 year history (Lewis, this volume), suggesting that human impacts have overwhelmed the natural forces at play.
Keywords: Boston Harbor; Coastal Embayment; Marine Organic Matter; Striped Bass; White Perch; dept.egm

Forest cover change in the northeastern U.S.: A spatial assessment in the context of an environmental kuznets curve - Bentley, George C; Cromley, Robert G; Hanink, Dean M; Heidkamp, C Patrick (International Journal of Applied Geospatial Research, 2013)
An analysis of the association of forest cover, treated as an environmental good, and income at the county scale in the Northeastern United States was conducted for 2006. Global analysis using a spatial error regression model indicates an environmental Kuznets curve (EKC) type of relationship, with total forest cover, percent forest cover, and forest cover per capita is better associated with per capita income and is better specified as a polynomial rather than in linear terms. Local analysis, using geographically weighted regression, indicates that sub-regional effects are pronounced, and that conformity to an EKC varies spatially and by forest cover measure. The findings should be interpreted strictly within their context of a cross-sectional analysis and within certain statistical limitations, primarily engendered by multicollinearity of the explanatory variables in the regression models. Copyright © 2013, IGI Global.
Keywords: Environmental Kuznets Curve; Forest Cover; Geographically Weighted Regression; Northeastern United States; Spatial Error Regression Model; dept.egm

Tax lien sales as local neoliberal governance strategy: The case of Waterbury, Connecticut - Botein, Hilary; Heidkamp, C Patrick (Local Economy, 2013)
This article examines bulk sales of municipal property tax liens in the formerly industrial city of Waterbury, Connecticut, USA, in the 1990s, in order to explore the limits and contradictions of neoliberal local governance strategies. In the USA, cities and states create property tax liens by reducing delinquent real estate taxes to a judgment that creates a legal claim against the property at issue. We argue that Waterbury's efforts to resolve its fiscal stress by enhancing short-term revenues ultimately further constrained its revenue base, the tax lien sales reflected a spatial selectivity that created barriers to revitalization when neither the city nor tax lien purchasers had incentives to foreclose on distressed properties in struggling neighborhoods, and the tax lien sales' failure to resolve the city's budget crisis set in motion new efforts at tax base enhancement through real estate-led development in the central business district that also were unsuccessful. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: dept.egm; housing; local government; neighbourhood decline; neoliberalism; real estate taxes; tax liens; urban governance

Use of aguadas as water management sources in two southern maya lowland sites - Ferrand, Ezgi Akpinar; Dunning, Nicholas P; Lentz, David L; Jones, John G (Ancient Mesoamerica, 2012)
Aguadas, either natural or human-made ponds, were significant sources of water for the ancient Maya. Aguadas are common features in the Maya Lowlands and make valuable locations for collecting archaeological and paleoenvironmental data. This article discusses research conducted at four aguadas around two adjacent Maya sites, San Bartolo and Xultun in Peten, Guatemala. Both San Bartolo and Xultun were established during the Preclassic period. However, the fates of the two sites differed, as Xultun continued to prosper while the city of San Bartolo was abandoned near the close of the Late Preclassic period. We argue that aguadas provide important clues for understanding the fate of these two ancient communities and many others in the Maya Lowlands. Copyright © 2012 Cambridge University Press.
Keywords: Guatemala [Central America]; Maya Lowlands; Peten; San Bartolo; archaeological evidence; dept.egm; paleoenvironment; planning history; urban planning; water management; water resource; water use

Where to begin? Getting started teaching GIS&T - West, Eric (Teaching Geographic Information Science and Technology in Higher Education, 2012)
Keywords: Coordinating lectures; Exercise style; Faculty teaching GIS&T; Global positioning system; Global positioning systems (GPS); Goals, for courses; Inquiry instruction; Learning objective, in BoK; Learning objectives; Teaching; Teaching GIS&T; dept.egm

‘Food desertification’: The loss of a major supermarket in New Haven, Connecticut - Russell, Scott E; Heidkamp, C Patrick (Applied Geography, 2011)
In March of 2010, the only full-service supermarket centrally located in New Haven, Connecticut closed, stranding many of the city's residents in a food desert. A food desert is an urban or rural area with significantly limited access to retail sources of healthy and affordable food, due to a combination of socioeconomic disadvantages and physical distance. This article considers the pivotal and causative role of the business model of supermarkets in the creation of new or exacerbation of current urban food deserts, as well as in the impact the loss of one market has on the resilience of the community's food system. Using the events of New Haven as a case study, the form and severity of the food desert in New Haven is analyzed by mapping 1/4 mile, 1/2 mile, and 1 mile road network service areas of the major supermarkets and grocery stores of the area. These are compared against Census block group data of the New Haven population's median household income, poverty level, and access to a personal vehicle. The results show certain parts of the city with low income, high poverty, and low vehicle access to exist in hardship outside the service areas of nearby stores. GIS methodology aids in illustrating the conclusion that the loss of just one supermarket has had significantly detrimental effects on the geographical food access of the city's residents. The ongoing lack of a full-service supermarket in the city not only raises concerns about the value of a new supermarket coming in, but also creates possibilities for seeking alternative food system solutions. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Connecticut; Food deserts; Food security; GIS; Geographic information systems (GIS); New Haven; Supermarkets; United States; Urban food systems; consumption behavior; dept.egm; food consumption; mapping method; retailing; spatial analysis

Astana, Kazakhstan: Megadream, Megacity, Megadestiny? - Yacher, Leon (Engineering Earth: The Impacts of Megaengineering Projects, 2011)
Astana, Kazakhstan’s new capital city is being built to fit the future vision of the country’s leaders. Unique architectural styles, combined with creative morphological patterns give the city a distinctive look. It is being constructed to impress. It also represents a break from the past. As such, Astana embodies the meaning of a ‘Forward city.’ Forward cities are created for a variety of reasons; political, geopolitical, religious, economic or a combination of these. By relocating a capital city elsewhere, a country seeks to construct a fresh urban site that reflects a change from the traditional center of governmental activities to a new location that reveals a new direction for the country and its people. This chapter provides a brief background of the political context and conditions existing in the region, followed by an overview of the city’s geographic base, and scrutinize the unique methods of finance used to construct Astana. Also, the planning and design of the city will be examined, paying special attention to the ways in which architecture has been utilized to construct a futuristic vision of a public project for domestic and international consumption.
Keywords: Capital City; Kyrgyz Republic; Presidential Decree; Soviet Republic; Special Economic Zone; dept.egm

Mobility, farmworkers, and Connecticut's tobacco valley, 1900–1950 - Harrison, Blake (Journal of Historical Geography, 2010)
By the early decades of the twentieth century, southern New England's Connecticut Valley had become a center of shade tobacco production and a destination for seasonal farmworkers drawn from sources inside and outside of New England. This paper explores the history of three groups of seasonal workers-children from area cities and towns; white southern high school students: and young African American men from southern high schools and black colleges-with an eye to assessing the impact of their presence on the form and meaning of the Connecticut Valley. My first goal is to add depth to the historiography of twentieth-century New England farming by drawing attention to the largely overlooked story of non-rural and extra-regional seasonal farmworkers. My second goal is to frame the case of Connecticut tobacco labor according to the study of mobility and its relationship to landscape. The mobility of workers into and within the region, I suggest, made possible the success of the shade tobacco economy while at the same time posing challenges to popularized cultural conventions about regional identity. For this reason, I argue, the history of Connecticut's shade tobacco landscape was informed by the efforts of shade tobacco growers to direct and control a confluence of environmental conditions, group and place-based identities, and the mechanics and meanings of mobility among seasonal workers. By hiring non-local, seasonal workers and by attempting to control their mobility, large-scale, corporate growers and their spokespeople ultimately sought to maintain control over the development and identity of the valley's rural landscape. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Agriculture; Connecticut; Connecticut Valley; Labor; Mobility; New England; Nicotiana tabacum; Tobacco; United States; agricultural production; dept.egm; environmental conditions; mobility; rural landscape; tobacco; twentieth century

Photojournal: distant beats: tradition and change in senegal - Yacher, Leon (Focus on Geography, 2010)
Keywords: Senegal; cultural change; cultural geography; cultural influence; cultural landscape; cultural tradition; dept.egm; music

Diel and tidal pCO2 × O2 fluctuations provide physiological refuge to early life stages of a coastal forage fish - Cross, Emma L.; Murray, Christopher S.; Baumann, Hannes (Scientific Reports, 2019)
Coastal ecosystems experience substantial natural fluctuations in pCO2 and dissolved oxygen (DO) conditions on diel, tidal, seasonal and interannual timescales. Rising carbon dioxide emissions and anthropogenic nutrient input are expected to increase these pCO2 and DO cycles in severity and duration of acidification and hypoxia. How coastal marine organisms respond to natural pCO2 × DO variability and future climate change remains largely unknown. Here, we assess the impact of static and cycling pCO2 × DO conditions of various magnitudes and frequencies on early life survival and growth of an important coastal forage fish, Menidia menidia. Static low DO conditions severely decreased embryo survival, larval survival, time to 50% hatch, size at hatch and post-larval growth rates. Static elevated pCO2 did not affect most response traits, however, a synergistic negative effect did occur on embryo survival under hypoxic conditions (3.0 mg L-1). Cycling pCO2 × DO, however, reduced these negative effects of static conditions on all response traits with the magnitude of fluctuations influencing the extent of this reduction. This indicates that fluctuations in pCO2 and DO may benefit coastal organisms by providing periodic physiological refuge from stressful conditions, which could promote species adaptability to climate change.
Keywords: dept.egm

The blue economy: Identifying geographic concepts and sensitivities - Garland, Michaela; Axon, Stephen; Graziano, Marcello; Morrissey, John; Heidkamp, C. Patrick (Geography Compass, 2019)
There is currently no generally accepted definition for the “blue economy,” despite the term becoming common parlance over the past decade. The concept and practice have spawned a rich, and diverse, body of scholarly activity. Yet despite this emerging body of literature, there is ambiguity around what the blue economy is, what it encapsulates, and its practices. Thus far, the existing literature has failed to theorise key geographical concepts such as space, place, scale, and power relations, all of which have the potential to lead to uneven development processes and regional differentiation. Previous research has sought to clarify the ontological separation of land and sea or has conceptualised the blue economy as a complex governmental project that opens up new governable spaces and rationalises particular ways of managing marine and coastal regions. More recently, geographers have called for a critical—and practical—engagement with the blue economy. This paper critically examines the existing literature of the geographies of the blue economy through a structured meta-analysis of published work, specifically its conceptualisations and applications to debates in the field. Results offer the potential to ground a bottom-up definition of the blue economy. In so doing, this paper provides a clearly identifiable rubric of the key geographical concepts that are often overlooked by researchers, policymakers, and practitioners when promoting economic development and technological innovation in coastal and marine environments. © 2019 The Author(s) Geography Compass © 2019 John Wiley & Sons Ltd
Keywords: coastal zone; conceptual framework; dept.egm; economic development; economics; innovation; marine environment; peer-reviewed; power relations; uneven development

Thicker shells compensate extensive dissolution in brachiopods under future ocean acidification - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Environmental Science & Technology, 2019)
Keywords: dept.egm; peer-reviewed

Development of an ecoregional floristic quality assessment method for the northeastern united states - Faberlangendoen, Don; Cameron, Don; Gilman, Arthur V; Metzler, Kenneth J; Ring, Richard M; Sneddon, Lesley (Northeastern Naturalist, 2019)
Floristic quality assessments (FQA) are widely used to assess ecological condition, based on plant species' coefficients of conservatism, or C values, but these values are typically assigned at the state level, limiting their regional consistency. We developed ecoregional C values (eC) using standard expert-based team review, partly informed by preexisting state C values for the 5 EPA ecoregions that cover New England and part of New York. We evaluated a total of 3686 taxa, with separate eC values for each ecoregion in which they occurred. We compared the performance of the C and eC values using the response of FQA metrics (mean C, cover-weighted mean C) to a disturbance gradient, based on readily available datasets in Maine and Vermont. The eC values typically performed moderately better than state values and provide a region-wide tool for assessment methods. All eC values are available on the Universal FQA website. © 2019 Humboldt Field Research Institute. All rights reserved.
Keywords: dept.egm; peer-reviewed

Robust quantification of fish early life CO2 sensitivities via serial experimentation - Baumann, Hannes; Cross, Emma L.; Murray, Chris S. (Biology Letters, 2018)
Keywords: dept.egm; peer-reviewed

Data and policy scale mismatch in coastal systems : The potential of μUAS as new tools for monitoring coastal resilience - Graves, Scott M. (Towards Coastal Resilience and Sustainability, 2018)
An important challenge in monitoring, planning and evaluating coastal saltmarsh resources in the face of predicted sea level rise (SLR) using numerical
Keywords: 3D modeling; Antennas; Coastal systems; Flight planning; Model results; Numerical models; Remotely sensed data; Scale mismatches; Sea level; Sea level rise; Structure from motion; Unmanned aerial systems; Unmanned aerial vehicles (UAV); Wetlands; dept.egm

Conclusion: Outlook for coastal transitions - Heidkamp, C. Patrick; Morrissey, John; Morrissey, John (Towards Coastal Resilience and Sustainability, 2018)
Globally, rapid demographic change of coastal urban agglomerations, the speed of urbanisation over time, the overall impact of coastal space occupation as well
Keywords: Climate change; Coastal ecosystems; Coastal zones; Demographic changes; Economics; Ecosystem services; Ecosystems; Energy availability; Flood control; Impervious surface; Long term process; Sea level; Topography; Urban agglomerations; Urban development; Urban growth; dept.egm

Harnessing place attachment for local climate mitigation? Hypothesising connections between broadening representations of place and readiness for change - Upham, Paul; Johansen, Katinka; Bögel, Paula Maria; Axon, Stephen; Garard, Jennifer; Carney, Sebastian (Local Environment, 2018)
Keywords: dept.egm; peer-reviewed

The human factor: Classification of European community-based behaviour change initiatives - Axon, Stephen; Morrissey, John; Aiesha, Rosita; Hillman, Joanne; Revez, Alexandra; Lennon, Breffní; Salel, Mathieu; Dunphy, Niall; Boo, Eva (Journal of Cleaner Production, 2018)
Behaviour, practices and culture constitute a powerful human factor in the energy system; in particular the interactions between technologies, practices and norms lock individuals in to certain patterns of (often inefficient) energy use. Consequently, behaviour change has gained traction amongst policy makers as a key area of intervention given the impact energy-related behaviours have on climate change. Given the increasing emphasis within policy perspectives in the European Union, it is surprising that a gap in understanding of the success factors of behaviour change initiatives remains. This paper addresses this gap by identifying and characterising behaviour change initiatives across five European countries (the UK, Ireland, France, Italy, and Spain). The paper provides insights into the success factors and commonly encountered barriers to behaviour change initiatives. Initiatives are classified into 6 broad categories (community-based interventions; information and awareness based interventions; eco-districts; show-case events; energy switching; and smart-technology focused interventions). The results suggest that there are significant knowledge gaps between what is known to work to engage individuals in behavioural change and what is currently being applied in practice. An over-reliance on education and awareness-raising projects is evident, illustrating that such projects do not sufficiently aim for sustained behavioural changes. A dearth of projects incorporating fiscal measures, regulations or legislation to drive behaviour change reflects reluctance on behalf of decision-makers to engage widely with diverse approaches to foster lifestyle change. This paper contributes understandings of the different models and delivery tools employed to change energy-related behaviours; insights into the critical success factors that underpin best practice and the barriers to action; and a `what works in practice' overview of the meaningful approaches to change behaviour. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Behaviour change; Behaviour changes; Binary alloys; Climate change; Decision making; Energy; Europe; Human engineering; Interventions; Laws and legislation; Potassium alloys; Practices; Sustainability; Sustainable development; Uranium alloys; dept.egm; peer-reviewed

A 120-year record of resilience to environmental change in brachiopods - Cross, Emma L.; Harper, Elizabeth M.; Peck, Lloyd S. (Global Change Biology, 2018)
Keywords: dept.egm; peer-reviewed

Social enterprise as a potential niche innovation breakout for low carbon transition - Hillman, Joanne; Axon, Stephen; Morrissey, John (Energy Policy, 2018)
While there is growing consensus that human behaviours need to change to a more sustainable paradigm, community driven approaches, such as social enterprise, have yet to be explored as serious instruments of sustainability transition. Social enterprises sit within the third sector of the economy, typically where market or governmental failures exist in the provision of social welfare, and have increasingly become a key driver of social progress. The autonomous nature of the social-economic model applied by such organisations can represent a viable means to reduce state social welfare dependence, and is a proven model for social change. The capability of social enterprises to create both social and economic value is considered a `win-win'. Yet there are clear potentials for social enterprise models to be more extensively applied to address contemporary ecological challenges of neo-liberal market economies, moving towards `win-win-win' outcomes across social, economic and ecological domains. This paper investigates the value of social enterprises as drivers of low-carbon transition at the community level, with an emphasis on the energy sector. Evidence from seven organisations in the UK is presented and a socio-technical transitions conceptual framework is applied to analyse these social enterprise operations as a form of social innovation.
Keywords: Behavioral research; Carbon; Commerce; Conceptual frameworks; Ecology; Energy; Innovation; Low-carbon transitions; Social Enterprise; Social enterprise; Social innovations; Socio-technical regimes; Socio-technical transitions; Sustainability Transitions; Sustainability transition; Sustainable development; United Kingdom; carbon; carbon emission; dept.egm; emission control; environmental economics; innovation; sustainability; welfare provision

A transitions perspective on coastal sustainability - Morrissey, John; Heidkamp, C. Patrick (Towards coastal resilience and sustainability, 2018)
This chapter presents a review of the multi-scalar complexities of coastal sustainability challenges. It focuses on three discrete vignettes of innovation, which range from a novel and emerging innovation, a maturing innovation and an innovation which has become mainstream and part of the prevailing socio-technical regime. The first vignette focuses on 3D ocean farming off the coast of Connecticut in Long Island Sound, USA, as an example of an emerging niche-level innovation. The second vignette discusses the development of offshore wind energy capacity in Liverpool Bay, UK as an example of a socio-technical innovation that is more mature. The final vignette discusses containerisation as an example of a fully matured socio-technological change. The chapter argues that a spatial perspective on transition is critical to adequately account for uneven development processes and to recognise the heterogeneity of different places in terms of potential for low-carbon transition. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Barium alloys; Coastal sustainability; Development process; Liverpool bays; Low-carbon transitions; Off-shore wind energy; Offshore oil well production; Socio-technical regimes; Sociotechnical; Sustainable development; Technological change; Wind power; dept.egm

Coastal sediment management as a response to intensifying storms and sea level rise: A case study - Tait, James; Orlowski, Ryan; Brewer, Jessica; Miller, Matthew D (Towards coastal resilience and sustainability, 2018)
In a period of rising sea levels and intensifying storms, enhancing coastal resilience and finding sustainable ways of living with the coast have become necessary concerns. Investigations of storm wave damage to coastal structures on the Connecticut shoreline during Hurricane Irene and Superstorm Sandy revealed that the width and height of frontal beaches were the most common denominator in mitigating the damages. One of the major problems, particularly for a state like Connecticut that has a highly developed coastline with systematically eroding beaches, is that the cost of beach nourishment projects is not only high but is increasing rapidly. The cost of beach nourishment at Prospect Beach in the town of West Haven is instructive. However, considering the importance of beaches and the costs of replenishment, rethinking Environmental Protection policies in favour of instituting regional and local sediment management practices may be in order. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Beach nourishment; Beach nourishment projects; Beaches; Coastal sediments; Coastal structures; Common denominators; Sea level; Sea level rise; Sediment management; Shore protection; Storm waves; Storms; Sustainable development; dept.egm

The human geographies of coastal sustainability transitions - Axon, Stephen (Towards coastal resilience and sustainability, 2018)
This chapter provides an overview of public engagement, its importance and effective approaches to meaningfully involve the public with coastal sustainability transitions. It presents two case studies, Guernsey, British Channel Islands and Cape Wind, Massachusetts. These illustrate how concepts of identity, marginality and engagement are essential to the development of coastal sustainability transitions. As the case study of Guernsey outlines, coastal sustainability transition-related public engagement should seek to enhance the local distinctiveness of coastal areas and 'fit within the wider narrative of place identity and how individuals feel attached to places that are ascribed with specific meanings'. Furthermore, as the case study of Cape Wind illustrates, coastal sustainability transitions need to connect with local communities in terms of addressing immediate social and economic concerns. Therefore, as a research agenda, the human geographies of coastal sustainability transitions can be of substantial value to the practical application of sustainability. © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Case-studies; Coastal sustainability; Economic concerns; Effective approaches; Local community; Massachusetts; Public engagement; Research agenda; Sustainable development; dept.egm

“Keeping the ball rolling”: Addressing the enablers of, and barriers to, sustainable lifestyles - Axon, Stephen (Journal of Environmental Psychology, 2017)
The impetus for addressing climate change is real and present, but its translation into action lacks immediacy and severity, and involves reorientating our lifestyles and economies towards sustainability. Drawing on focus groups conducted in seven UK communities, specific interventions were identified as encouraging change in the short-term, maintaining momentum in the medium-term and sustaining sustainability in the long-term to address various enablers of, and barriers to, sustainable lifestyles. The findings illustrate that there are multiple entry points and influencing periods for sustainable living. Given the importance of the temporal dimension in encouraging and sustaining practices for sustainable lifestyles, the paper advances a “what works” approach to sustainable lifestyles that can be embedded with practical solutions. This approach creates a synergy between what individuals want to do to live sustainably and how they want to do this with interventions that are known to create meaningful lifestyles changes and maintain sustainable living.
Keywords: Addressing climate change; Barriers; Enablers; Interventions; Social practices; Sustainable lifestyles; dept.egm

Land-use change at temporary group-housing sites in post-Katrina Louisiana - Zavar, Elyse; Hagelman, III, Ronald; Lavy, Brendan; Prince, Benjamin (Natural Hazards Review, 2017)
To shelter the large number of displaced households following Hurricane Katrina (2005), FEMA, in conjunction with local governments, established 110 temporary group-housing sites throughout impacted Louisiana. The purpose of this study is to identify how temporary group-housing sites influenced the land use of post-Katrina Louisiana. Using aerial imagery, this study assessed the land use of each temporary group-housing site prior to Hurricane Katrina in 2005 and again in 2010. Of the 110 group-housing sites, 54.5% reverted to the previous land use, 29.1% returned to the previous land use with improvements, and 16.3% of the sites changed land use. Using census data from 2000 and 2010, site characteristics, and property records, this study employed a multinomial logistic regression to identify statistically significant variables in predicting land-use change in post-Katrina Louisiana. The results indicate that, especially in neighborhoods with high demand for land, FEMA temporary group-housing sites tended to be redeveloped into new land uses.
Keywords: Aerial imagery; Aerial photography; Group housing; Housing; Hurricane Katrina; Hurricane Katrina 2005; Hurricane katrina; Hurricanes; Land use; Land-use change; Local government; Louisiana; Multinomial logistic regression; Population statistics; Significant variables; Site characteristics; Temporary group housing; United States; aerial photograph; census; dept.egm; hazard assessment; hazard management; housing project; land use change; local government; neighborhood

Geospatial sculpture: Nonverbal communication through the tactilization of geospatial data - Heidkamp, C. Patrick; Slomba, Jeffrey T. (GeoHumanities, 2017)
Keywords: 3D visualization; Connecticut; Escultura Geoespacial; GeoSpatial Sculpture; dept.art; dept.egm; geografías no verbales; nonverbal geographies; peer-reviewed; tactilización; tactilization; visualización en 3D; 三维可视化; 地理空间雕塑; 康涅狄格; 触觉化; 非语言的地理